Solid electrolytic capacitor containing polyaniline

By forming a dielectric, precoat and solid electrolyte layer of a specific conductive polymer on the porous anode body, the problems of leakage current and capacitance loss in existing solid electrolytic capacitors under high voltage and wet environments are solved, and the stability of electrical performance at high temperatures and low equivalent series resistance is achieved.

CN114467160BActive Publication Date: 2025-04-01KYOCERA AVX COMPONENTS CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202180005465.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-13
Filing Date
2021-02-10
Publication Date
2025-04-01
Estimated Expiration
2041-02-10

AI Technical Summary

Technical Problem

Existing solid electrolytic capacitors exhibit high leakage current and capacitance losses under high voltage and wet environments, and their electrical performance is unstable under high temperature conditions.

Method used

Using a capacitor element containing a conductive polymer, repeating units of the conductive polymer are derived from aniline monomers with a specific general formula and a dielectric, precoat and solid electrolyte layers are formed on the porous anode body.

Benefits of technology

Low leakage current and high capacitance recovery rate in high voltage and wet environments are achieved, and the capacitance remains stable under high temperature conditions, and the equivalent series resistance and dissipation coefficient are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114467160B_ABST
    Figure CN114467160B_ABST
Patent Text Reader

Abstract

A solid electrolytic capacitor comprising a capacitor element is provided. The capacitor element comprises: a sintered porous anode body; a dielectric overlying the anode body; a precoat layer overlying the dielectric; and a solid electrolyte overlying the precoat layer. The solid electrolyte comprises a conductive polymer having repeating units derived from an aniline monomer having the general formula (I):
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 62 / 975,975, filed on February 13, 2020, which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to a solid electrolytic capacitor containing polyaniline. Background Art

[0004] Solid electrolytic capacitors (e.g., tantalum capacitors) are typically made by pressing a metal powder (e.g., tantalum) around a metal lead, sintering the pressed part, anodizing the sintered anode, and then applying a solid electrolyte. Intrinsically conductive polymers are often used as solid electrolytes due to their advantageous low equivalent series resistance ("ESR") and "no burn / no ignition" failure mode. For example, such electrolytes can be formed by in situ chemical polymerization of 3,4-dioxythiophene monomer ("EDOT") in the presence of a catalyst and a dopant. However, conventional capacitors using in situ polymerized polymers tend to have relatively high leakage current ("DCL") and fail at high voltages, such as experienced during rapid turn-on or operating current spikes. To overcome these problems, dispersions formed from complexes of poly(3,4-ethylenedioxythiophene) and poly(styrene sulfonic acid) ("PEDOT:PSS") have also been employed. While PEDOT:PSS dispersions can lead to improved leakage current values, other problems remain. For example, one problem with capacitors based on polymer slurries is that they can only achieve a relatively low percentage of their wet capacitance, meaning that they have relatively large capacitance losses and / or fluctuations in the presence of atmospheric humidity.

[0005]

[0006] Therefore, there is a need for improved solid electrolytic capacitors that exhibit relatively stable electrical properties. Summary of the invention

[0006] According to one embodiment of the present invention, a solid electrolytic capacitor comprising a capacitor element is disclosed. The capacitor element comprises: a sintered porous anode body, a dielectric overlying the anode body, a pre-coat overlying the dielectric, and a solid electrolyte overlying the pre-coat. The solid electrolyte comprises a conductive polymer having repeating units derived from an aniline monomer having the following general formula (I):

[0007]

[0008] in,

[0009] R5 and R6 are independently hydrogen, alkyl, alkenyl, aryl, alkoxy, aryloxy, alkylthioalkyl, alkaryl, aralkyl, haloalkyl, amino, epoxy, silane, siloxane, alcohol, benzyl, carboxylate, ether, ether carboxylate, ether sulfonate, ester sulfonate, carbamate, or a combination thereof.

[0010] Other features and aspects of the present invention are described in more detail below. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In the remainder of this specification, a more particular description is given of a complete and enabling disclosure of the invention, including the best mode thereof, to one of ordinary skill in the art, with reference to the accompanying drawings, in which:

[0012] Figure 1 A cross-sectional view of one embodiment of a capacitor of the assembly of the present invention;

[0013] Figure 2 A cross-sectional view of another embodiment of a capacitor of the assembly of the present invention;

[0014] Figure 3 A cross-sectional view of yet another embodiment of a capacitor that is an assembly of the present invention; and

[0015] Figure 4 A top view of another embodiment of a capacitor of the assembly of the present invention is shown.

[0016] Repeated use of reference characters in the present specification and drawings is intended to represent the same or analogous features or elements of the present invention. DETAILED DESCRIPTION

[0017] Those skilled in the art will appreciate that the present discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention, which are embodied in the exemplary configurations.

[0018] In general, the present invention relates to a solid electrolytic capacitor comprising a capacitor element, the capacitor element comprising a porous anode body, a dielectric overlying the anode body, a pre-coating overlying the dielectric, and a solid electrolyte overlying the pre-coating. To help facilitate the use of the capacitor in high voltage applications, the solid electrolyte comprises a conductive polymer comprising repeating aniline units of the following general formula (I):

[0019]

[0020] Wherein, R5 and R6 are independently hydrogen, alkyl, alkenyl, aryl, alkoxy, aryloxy, alkylthioalkyl, alkaryl, aralkyl, haloalkyl, amino, epoxy, silane, siloxane, alcohol, benzyl, carboxylate, ether, ether carboxylate, ether sulfonate, ester sulfonate, carbamate, or a combination thereof. In addition, the pre-coating can help stabilize the solid electrolyte, especially at high temperatures.

[0021] Without intending to be limited by theory, it is believed that such materials can help the resulting capacitor maintain stable electrical properties (e.g., capacitance) under a variety of different conditions. For example, the capacitor can exhibit a high percentage of its wet capacitance, which allows the capacitor to have only a small capacitance loss and / or fluctuation in the presence of atmospheric humidity. This performance characteristic is quantified by "capacitance discovery," which is determined by the following equation:

[0022] Recovery rate (%) = (dry capacitance / wet capacitance) × 100

[0023] The capacitor may exhibit about 50% recovery or more, in some embodiments about 60% recovery or more, in some embodiments about 70% recovery or more, and in some embodiments about 80% to 100% recovery.

[0024] The capacitance can remain stable even after long exposure to high temperatures, such as about 80°C or higher, in some embodiments, about 100°C to about 150°C, and in some embodiments, about 105°C to about 130°C (e.g., 105°C or 125°C), such as about 100 hours or longer, and in some embodiments, about 150 hours to about 3000 hours (e.g., 240 hours). In one embodiment, for example, the ratio of the capacitance after exposure to high temperature (e.g., 105°C) for 240 hours to the initial capacitance value (e.g., at 23°C) is about 0.7 to 1, in some embodiments, about 0.8 to 1, in some embodiments, about 0.9 to 1, and in some embodiments, 0.91 to 0.99. The actual capacitance value (dry) may vary, but is typically about 1 millifarad per square centimeter ("mF / cm2") measured at a frequency of 120 Hz. 2 ”) or more, in some embodiments about 2 mF / cm 2 or more, in some embodiments about 5 mF / cm 2 To about 50mF / cm 2 , and in some embodiments about 8 mF / cm 2 To about 20mF / cm 2 .

[0025] The capacitor may also exhibit a relatively high "breakdown voltage" (the voltage at which the capacitor fails), such as about 85 volts or more, in some embodiments about 90 volts or more, in some embodiments about 95 volts or more, and in some embodiments about 100 volts to about 300 volts, such as determined by increasing the applied voltage in 3 volt increments until the leakage current reaches 1 mA. Likewise, the capacitor may also be able to withstand relatively high surge currents, which are also common in high voltage applications. For example, the peak surge current may be about 100 amperes or more, in some embodiments about 200 amperes or more, and in some embodiments, about 300 amperes to about 800 amperes.

[0026] In addition to those mentioned above, the capacitor can also exhibit other improved electrical properties. For example, after being subjected to an applied voltage (e.g., 120 volts) for a period of time, the capacitor can exhibit a leakage current ("DCL") of only about 100 microamperes ("μA") or less, in some embodiments, about 70μA or less, and in some embodiments, about 1μA to about 50μA. It is worth noting that the capacitor can exhibit such low DCL values ​​even under dry conditions such as those described above. The capacitor can also exhibit a relatively low equivalent series resistance ("ESR"), such as an equivalent series resistance measured at an operating frequency of 100kHz and a temperature of 23°C of about 200 milliohms, in some embodiments less than about 150 milliohms, in some embodiments about 0.01 milliohms to about 125 milliohms, and in some embodiments about 0.1 milliohms to about 100 milliohms. The capacitor may exhibit such an ESR value even after prolonged exposure to a temperature of about 80°C or higher, in some embodiments about 100°C to about 150°C, and in some embodiments about 105°C to about 130°C (e.g., 105°C or 125°C), for example, about 100 hours or more, and in some embodiments about 150 hours to about 3,000 hours (e.g., 3,000 hours). In one embodiment, for example, the ratio of the ESR of the capacitor after 3,000 hours of exposure to high temperature (e.g., 105°C) to the initial ESR value of the capacitor (e.g., at 23°C) is about 2.0 or less, in some embodiments about 1.5 or less, and in some embodiments 1.0 to about 1.3.

[0027] It is also believed that the dissipation factor of the capacitor can be kept at a relatively low level. The dissipation factor generally refers to the losses that occur in a capacitor and is often expressed as a percentage of an ideal capacitor performance. For example, as determined at a frequency of 120 Hz, the dissipation factor of the capacitor is typically about 250% or less, in some embodiments about 200% or less, and in some embodiments about 1% to about 180%.

[0028] Various embodiments of the capacitor will now be described in more detail.

[0029] I. Capacitor Components

[0030] A. Anode

[0031] The capacitor element includes an anode comprising a dielectric formed on a sintered porous body. The porous anode body can be formed of a powder comprising a valve metal (i.e., a metal capable of oxidation) or a valve metal compound (e.g., tantalum, niobium, aluminum, hafnium, titanium, alloys thereof, oxides thereof, and nitrides thereof, etc.). The powder is typically formed by a reduction process in which a tantalum salt (e.g., potassium fluorotantalate (K2TaF7), sodium fluorotantalate (Na2TaF7), tantalum pentachloride (TaCl5), etc.) reacts with a reducing agent. The reducing agent can be provided in the form of a liquid, a gas (e.g., hydrogen), or a solid (e.g., a metal (e.g., sodium), a metal alloy, or a metal salt). In one embodiment, for example, a tantalum salt (e.g., TaCl5) may be heated at a temperature of about 900°C to about 2,000°C, in some embodiments about 1,000°C to about 1,800°C, and in some embodiments about 1,100°C to about 1,600°C to form a vapor that may be reduced in the presence of a gaseous reducing agent (e.g., hydrogen). Additional details of such a reduction reaction may be Maeshima et al. After reduction, the product can be cooled, crushed and washed to form a powder.

[0032] Depending on the desired application, the specific charge of the powder typically varies from about 2,000 to about 600,000 microfarads*volts / gram ("μF*V / g"). For example, in certain embodiments, a high charge powder may be employed, having a specific charge of about 100,000 to about 600,000 μF*V / g, in some embodiments about 120,000 to about 500,000 μF*V / g, and in some embodiments about 150,000 to about 400,000 μF*V / g. In other embodiments, a low charge powder may be employed, having a specific charge of about 2,000 to about 100,000 μF*V / g, in some embodiments about 5,000 to about 80,000 μF*V / g, and in some embodiments about 10,000 to about 70,000 μF*V / g. As is known in the art, specific charge can be determined by multiplying the capacitance by the anodization voltage employed and then dividing that product by the weight of the anodized electrode body.

[0033] Powder can be a free-flowing, finely divided powder comprising primary particles. For example, optionally after the particles are subjected to 70 seconds of ultrasonic vibration, the laser particle size distribution analyzer (e.g., LS-230) manufactured by BECKMAN COULTER Corporation is used to determine that the median size (D50) that the primary particles of the powder usually have is about 5 to about 500 nanometers, about 10 to about 400 nanometers in some embodiments, and about 20 to about 250 nanometers in some embodiments. Primary particles typically have a three-dimensional particle shape (e.g., nodular or angular). Such particles typically have a relatively low "aspect ratio (aspect ratio)", which is the average diameter or width of the particles divided by the average thickness ("D / T") . For example, the aspect ratio of the particles can be about 4 or less, about 3 or less in some embodiments, and about 1 to about 2 in some embodiments. In addition to primary particles, powder can also include other types of particles, such as secondary particles formed by agglomerating (or agglomerating) primary particles. Such secondary particles may have a median size (D50) of from about 1 micron to about 500 microns, and in some embodiments, from about 10 microns to about 250 microns.

[0034] Agglomeration of the particles can occur by heating the particles and / or by using a binder. For example, agglomeration can occur at a temperature of about 0°C to about 40°C, in some embodiments about 5°C to about 35°C, and in some embodiments about 15°C to about 30°C. Suitable binders may also include, for example, poly(vinyl butyral); poly(vinyl acetate); poly(vinyl alcohol); poly(vinyl pyrrolidone); cellulosic polymers such as carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose and methyl hydroxyethyl cellulose; random polypropylene, polyethylene; polyethylene glycol (e.g., Carbowax from Dow Chemical Co.); polystyrene, poly(butadiene / styrene); polyamides, polyimides and polyacrylamides, high molecular weight polyethers; copolymers of ethylene oxide and propylene oxide; fluoropolymers such as polytetrafluoroethylene, polyvinylidene fluoride, and fluoroolefin copolymers; acrylic polymers such as sodium polyacrylate, poly(lower alkyl acrylates), poly(lower alkyl methacrylates), and copolymers of lower alkyl acrylates and methacrylates; and fatty acids and waxes such as stearic acid and other soapy fatty acids, vegetable waxes, microcrystalline waxes (purified paraffin waxes), and the like.

[0035] The resulting powder can be compacted to form pellets using any conventional powder compacting equipment. For example, a press die can be used, which is a single station compaction press comprising a die and one or more punches. Alternatively, an anvil type compaction press using only a die and a single lower punch can be used. There are several basic types of single station compaction presses available, such as cam presses, toggle / knuckle presses, and eccentric / crank presses with multiple functions (e.g., single action, double action, floating die, movable platen, opposed ram, screw, impact, hot pressing, coining, or sizing). The powder can be compacted around an anode lead, which can be in the form of a wire, a sheet, or the like. The lead wire may extend longitudinally from the anode body and may be formed of any conductive material (e.g., tantalum, niobium, aluminum, hafnium, titanium, etc., and conductive oxides and / or nitrides thereof). Connection of the lead wire to the anode body may also be achieved using other known techniques, such as by welding the lead wire to the anode body or embedding the lead wire within the anode body during formation (e.g., prior to compaction and / or sintering).

[0036] After pressing, any binder can be removed by heating the pellets under vacuum at a temperature (e.g., about 150° C. to about 500° C.) for several minutes. Alternatively, the binder can also be removed by contacting the pellets with an aqueous solution, such as Bishop et al. 6,197,252 of the United States Patent No. . Afterwards, the pellets are sintered to form a porous integral mass. The pellets are typically sintered at a temperature of about 700°C to about 1800°C, about 800°C to about 1700°C in some embodiments, and about 900°C to about 1400°C for about 5 minutes to about 100 minutes, and about 8 minutes to about 15 minutes in some embodiments. This can occur in one or more steps. If necessary, sintering can occur in an atmosphere that limits the transfer of oxygen atoms to the anode. For example, sintering can occur in a reducing atmosphere, such as in a vacuum, an inert gas, hydrogen, etc. The pressure of the reducing atmosphere can be about 10 torr to about 2000 torr, about 100 torr to about 1000 torr in some embodiments, and about 100 torr to about 930 torr in some embodiments. A mixture of hydrogen and other gases (e.g., argon or nitrogen) can also be used.

[0037] B. Dielectric

[0038] The anode is also coated with a dielectric. As described above, the dielectric is formed by anodizing ("anodizing") the sintered anode so that a dielectric layer is formed over and / or within the anode. For example, a tantalum (Ta) anode can be anodized to tantalum pentoxide (Ta2O5).

[0039] Typically, anodization is performed by initially applying an electrolyte to the anode, such as by immersing the anode in the electrolyte. The electrolyte is usually in liquid form, such as a solution (eg, aqueous or non-aqueous), dispersion, melt, or the like. Solvents are commonly used in electrolytes, such as water (e.g., deionized water); ethers (e.g., diethyl ether and tetrahydrofuran); glycols (e.g., ethylene glycol, propylene glycol, etc.); alcohols (e.g., methanol, ethanol, n-propanol, isopropanol, and butanol); triglycerides; ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate, and methoxypropyl acetate); amides (e.g., dimethylformamide, dimethylacetamide, dimethylcaprylic / capric fatty acid amide, and N-alkylpyrrolidones); nitriles (e.g., acetonitrile, propionitrile, butyronitrile, and benzonitrile); and sulfoxides or sulfones (e.g., dimethyl sulfoxide (DMSO) and sulfolane), etc. The solvent may constitute about 50 wt.% to about 99.9 wt.% of the electrolyte, about 75 wt.% to about 99 wt.% in some embodiments, and about 80 wt.% to about 95 wt.% in some embodiments. Although not required, it is often desirable to use an aqueous solvent (e.g., water) to promote the formation of oxides. In fact, water may constitute about 1 wt.% or more of the solvent used in the electrolyte, about 10 wt.% or more in some embodiments, about 50 wt.% or more in some embodiments, about 70 wt.% or more in some embodiments, and about 90 wt.% to 100 wt.% in some embodiments.

[0040] The electrolyte is electrically conductive and has an electrical conductivity of about 1 millisiemens / cm ("mS / cm") or greater, in some embodiments about 30 mS / cm or greater, and in some embodiments about 40 mS / cm to about 100 mS / cm, as determined at a temperature of 25°C. To enhance the electrical conductivity of the electrolyte, an ionic compound that can dissociate in a solvent to form ions is generally employed. Suitable ionic compounds for this purpose may include, for example, acids such as nitric acid, sulfuric acid, phosphoric acid, polyphosphoric acid, boric acid, boronic acid, acid), etc.; organic acids, including carboxylic acids, such as acrylic acid, methacrylic acid, malonic acid, succinic acid, salicylic acid, sulfosalicylic acid, adipic acid, maleic acid, malic acid, oleic acid, gallic acid, tartaric acid, citric acid, formic acid, acetic acid, glycolic acid, oxalic acid, propionic acid, phthalic acid, isophthalic acid, glutaric acid, gluconic acid, lactic acid, aspartic acid, glutamic acid, itaconic acid, trifluoroacetic acid, barbituric acid, cinnamic acid, benzoic acid, 4-hydroxybenzoic acid, aminobenzoic acid, etc.; sulfonic acids, such as methanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, styrenesulfonic acid, naphthalene disulfonic acid, hydroxybenzenesulfonic acid, dodecylsulfonic acid, dodecylbenzenesulfonic acid, etc.; polymeric acids, such as poly(acrylic acid) or poly(methacrylic acid) and copolymers thereof (e.g., maleic acid-acrylic acid copolymer, sulfonic acid-acrylic acid copolymer and styrene-acrylic acid copolymer), carageenic acid, carboxymethyl cellulose, alginic acid, etc.; and the like. The concentration of the ionic compound is selected to achieve the desired conductivity. For example, the acid (e.g., phosphoric acid) can constitute from about 0.01 wt.% to about 5 wt.%, in some embodiments from about 0.05 wt.% to about 0.8 wt.%, and in some embodiments from about 0.1 wt.% to about 0.5 wt.% of the electrolyte. If desired, a blend of ionic compounds can also be used in the electrolyte.

[0041] To form the dielectric, typically, current is passed through the electrolyte while the electrolyte is in contact with the anode body. The value of the formation voltage controls the thickness of the dielectric layer. For example, the power supply can be initially set to constant current mode until the desired voltage is reached. Afterwards, the power supply can be switched to constant potential mode to ensure that the desired dielectric thickness is formed over the entire surface of the anode. Of course, other known methods, such as pulsed constant potential method or step-type constant potential method, can also be used. The voltage range at which anodization occurs is typically from about 4V to about 250V, and in some embodiments from about 5V to about 200V, and in some embodiments from about 10V to about 150V. During oxidation, the electrolyte can be maintained at an elevated temperature, such as about 30°C or higher, in some embodiments from about 40°C to about 200°C, and in some embodiments from about 50°C to about 100°C. Anodic oxidation can also be performed at ambient temperature or lower. The resulting dielectric layer can be formed on the surface of the anode and in the pores of the anode.

[0042] Although not required, in some embodiments, the dielectric layer can have different thicknesses throughout the anode because the dielectric layer has a first portion covering the outer surface of the anode and a second portion covering the inner surface of the anode. In such an embodiment, the first portion is selectively formed so that the thickness of the first portion is greater than the thickness of the second portion. However, it should be understood that the thickness of the dielectric layer does not need to be uniform in a specific area. For example, some portions of the dielectric layer adjacent to the outer surface may actually be thinner than some portions of the layer at the inner surface, and vice versa. Nevertheless, the dielectric layer can be formed so that at least a portion of the layer at the outer surface has a greater thickness than at least a portion at the inner surface. Although the exact differences in these thicknesses can vary depending on the specific application, the ratio of the thickness of the first portion to the thickness of the second portion is typically about 1.2 to about 40, about 1.5 to about 25 in some embodiments, and about 2 to about 20 in some embodiments.

[0043] In order to form a dielectric layer with different thicknesses, a multi-stage process can be used. At each stage of the process, the sintered anode is anodized ("anodized") to form a dielectric layer (e.g., tantalum pentoxide). During the first stage of anodization, a relatively small formation voltage is typically used to ensure that the desired dielectric thickness for the internal region is achieved, such as a voltage ranging from about 1 to about 90 volts, about 2 to about 50 volts in some embodiments, and about 5 to about 20 volts in some embodiments. Afterwards, the sintered body can then be anodized in the second stage of the process to increase the thickness of the dielectric to a desired level. This is typically accomplished by anodizing in an electrolyte at a voltage higher than the voltage used during the first stage, such as anodizing at a formation voltage ranging from about 50 to about 350 volts, about 60 to about 300 volts in some embodiments, and about 70 to about 200 volts in some embodiments. During the first stage and / or the second stage, the electrolyte may be maintained at a temperature ranging from about 15°C to about 95°C, in some embodiments from about 20°C to about 90°C, and in some embodiments from about 25°C to about 85°C.

[0044] The electrolyte used during the first and second stages of the anodizing process may be the same or different. However, typically, the electrolyte used during at least one stage of the dielectric development process comprises an ionic compound as explained above. In a particular embodiment, it may be desirable that the electrolyte used in the second stage has an ionic conductivity lower than that of the electrolyte used in the first stage to prevent the formation of a large amount of oxide film on the inner surface of the anode. In this regard, the electrolyte used during the first stage may comprise an ionic compound, which is an acid such as nitric acid, sulfuric acid, phosphoric acid, polyphosphoric acid, boric acid, boric acid, etc. Such an electrolyte may have a conductivity of about 0.1 to about 100 mS / cm, in some embodiments about 0.2 to about 20 mS / cm, and in some embodiments about 1 to about 10 mS / cm determined at a temperature of 25°C. The electrolyte used during the second stage may also comprise an ionic compound, which is a salt of a weak acid, so that the concentration of hydronium ions in the pores increases due to the charge passage therein. Ion transport or diffusion causes weak acid anions to move to the pores as required to balance charge. As a result, in the balance between hydronium ions, acid anions and undissociated acid, the concentration of the main conductive material (hydronium ion) is reduced, so that a poorly conductive material is formed. The reduction in the concentration of conductive material causes a relatively high voltage drop in the electrolyte, which hinders further anodization in the interior, and sets up a thicker oxide layer on the outside to reach a higher formation voltage in the region of continuous high conductivity. Suitable weak acid salts can, for example, include ammonium salts or alkali metal salts (for example, sodium, potassium, etc.) of boric acid, boric acid, acetic acid, oxalic acid, lactic acid, adipic acid, etc. Particularly suitable salts include sodium tetraborate and ammonium pentaborate. Such electrolytes typically have a conductivity of about 0.1 to about 20 mS / cm, about 0.5 to about 10 mS / cm, about 1 to about 5 mS / cm, determined at a temperature of 25 ° C, in some embodiments.

[0045] If necessary, each stage of anodization can be repeated for one or more cycles to obtain the desired dielectric thickness. In addition, after the first stage and / or the second stage, the anode can also be cleaned or washed with another solvent (e.g., water) to remove the electrolyte.

[0046] C. Pre-coating

[0047] As described above, a pre-coating layer is also used overlying the dielectric and between the dielectric and the solid electrolyte. The pre-coating layer may comprise one or more layers and may be formed from a variety of different materials. In one embodiment, for example, the pre-coating layer may comprise an organometallic compound, such as a compound having the following general formula (II):

[0048]

[0049] in,

[0050] Z is an organic metal atom, such as silicon and titanium;

[0051] R1, R2 and R3 are independently alkyl (e.g., methyl, ethyl, propyl, etc.) or hydroxyalkyl (e.g., hydroxymethyl, hydroxyethyl, hydroxypropyl, etc.), wherein at least one of R1, R2 and R3 is hydroxyalkyl;

[0052] n is an integer from 0 to 8, in some embodiments an integer from 1 to 6, and in some embodiments an integer from 2 to 4 (e.g., 3); and,

[0053] X is an organic or inorganic functional group, such as glycidyl, glycidyloxy, mercapto, amino, vinyl, and the like.

[0054] In certain embodiments, at least one of R1, R2 and R3 in formula (II) may be a hydroxyalkyl group (e.g., OCH3). For example, each of R1, R2 and R3 may be a hydroxyalkyl group. However, in other embodiments, R1 may be an alkyl group (e.g., CH3) and R2 and R3 may be a hydroxyalkyl group (e.g., OCH3).

[0055] In certain embodiments, X may be an amino group. Suitable amino-functional silane compounds may include, for example, monoamino-functional silanes having the following general formula (III):

[0056]

[0057] in,

[0058] R1, R2 and R3 are as defined above;

[0059] R4 and R5 are independently hydrogen, alkyl, independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halogen, haloalkyl, hydroxyalkyl, or alternatively N, R4 and R5 together with one or more additional atoms form a ring structure (e.g., heteroaryl or heterocyclyl); and

[0060] Z is an organic group that connects the nitrogen atom to the silicon atom, such as an alkyl group (eg, ethyl or propyl), an aryl group (eg, phenyl), or the like.

[0061] Examples of monoamino-functionalized silane compounds may include, for example, primary amine compounds (e.g., 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 4-aminobutyltriethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, aminophenyltrimethoxysilane, 3-aminopropyltri(methoxy-ethoxy)silane, 11-aminoundecyltriethoxysilane, 2(4-pyridylethyl)triethoxysilane, 2-(trimethoxysilylethyl)pyridine, N-(3-trimethoxysilylpropyl)pyrrole, 3-(m-aminophenoxypropyltrimethoxysilane), aminopropylsilanetriol, 3-aminopropylmethyldiethoxysilane, 3-aminopropyldiisopropylethoxysilane, 3-aminopropyldimethylethoxysilane, etc.); Secondary amine compounds (e.g., N-butylaminopropyltrimethoxysilane, N-ethylaminoisobutyltrimethoxysilane, N-methylaminopropyltrimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, (cyclohexylaminomethyl)triethoxysilane, N-cyclohexylaminopropyltrimethoxysilane, N-ethylaminoisobutylmethyldiethoxysilane, (phenylaminoethyl)methyl-diethoxysilane, N-phenylaminomethyltrimethoxysilane, N-methylaminopropylmethyl-dimethoxysilane, etc.); tertiary amine compounds (e.g., bis(2-hydroxyethyl)3-aminopropyltriethoxysilane, diethylaminomethyltriethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, etc.); and combinations thereof. In addition, if desired, additional groups may be bonded to the nitrogen atom so that the compound is a quaternary amine functionalized silane compound.

[0062] Diamino-functional silane compounds may also be employed, such as those having the following general formula (IV):

[0063]

[0064] in,

[0065] R1, R2, R3, R4 and R5 are as defined above; and

[0066] Z1 is an organic group connecting the nitrogen atom to the silicon atom, and Z2 is an organic group connecting the nitrogen atom, such as an alkyl group (e.g., ethyl or propyl group), an aryl group (e.g., phenyl group), etc. Examples of such diamino-functional silane compounds may include, for example, N-(2-aminoethyl)-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(6-aminohexyl)aminomethyl-triethoxysilane, N-(6-aminohexyl)amino-propyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane), (aminoethylaminomethyl)-phenethyltrimethoxysilane, N-3-(2-aminoethyl)-11-aminoundecyltrimethoxysilane. [(Amino(polypropoxy)]-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylsilanetriol, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, (aminoethylamino)-3-isobutyldimethylmethoxysilane, and the like, and combinations thereof. Triamino-functionalized compounds such as (3-trimethoxysilylpropyl)-diethylenetriamine may also be used.

[0067] Of course, as described above, other functional groups may also be used. For example, sulfur-functionalized silane compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2,2-dimethoxy-1-thia-2-silacyclopentane, 11-mercaptoundecyltrimethoxysilane, S-(octanoyl)mercaptopropyltriethoxysilane, 2-(2-pyridylethyl)thiopropyl-trimethoxysilane, 2-(4-pyridylethyl)thiopropyltrimethoxysilane, 3-thiocyanopropyltrimethoxysilane, may be used in certain embodiments. Propyltrimethoxysilane, 2-(3-trimethoxysilylpropylthio)-thiophene, mercaptomethylmethyldiethoxysilane, 3-mercaptopropylmethyldimethoxysilane, bis[3-(triethoxysilyl)propyl]tetrasulfide, bis[3-(triethoxysilyl)propyl]disulfide, bis[m-(2-triethoxysilylethyl)tolyl]polysulfide, bis[3-(triethoxysilyl)propyl]thiourea, and the like, and combinations thereof.

[0068] In addition to or in place of the organometallic compound, the pre-coating layer may also include one or more layers comprising an intrinsically conductive polymer having a positive charge located on the backbone that is at least partially compensated by anions covalently bound to the polymer. Any of a variety of intrinsically conductive polymers may generally be employed. For example, the intrinsically conductive polymer may be an intrinsically conductive thiophene polymer comprising repeating thiophene units. An embodiment of a suitable intrinsically conductive polymer may have repeating thiophene units of the following formula (V):

[0069]

[0070] in,

[0071] R is (CH2) a -O-(CH2) b -L, where L is a bond or HC([CH2] c H);

[0072] a is 0 to 10, in some embodiments 0 to 6, and in some embodiments 1 to 4 (e.g., 1);

[0073] b is 1 to 18, in some embodiments 1 to 10, and in some embodiments 2 to 6 (e.g., 2, 3, 4, or 5);

[0074] c is 0 to 10, in some embodiments 0 to 6, and in some embodiments 1 to 4 (e.g., 1);

[0075] M is an anion, such as SO3, C(O)O, BF4, CF3SO3, SbF6, N(SO2CF3)2, C4H3O4, ClO4, etc.;

[0076] X is a cation such as hydrogen, an alkali metal (eg, lithium, sodium, rubidium, cesium, or potassium), ammonium, or the like.

[0077] In a specific embodiment, M in formula (V) is a sulfonate ion. In formula (V), a is preferably 1, and b is preferably 3 or 4. Likewise, X is preferably sodium or potassium.

[0078] If desired, polymer can be a copolymer comprising other types of repeating units. In such an embodiment, the repeating unit of formula (V) typically constitutes about 50mol.% or more of the total amount of repeating units in the copolymer, in some embodiments about 75mol.% to about 99mol.%, and in some embodiments about 85mol.% to about 95mol.%. Of course, polymer can also be a homopolymer, so that the polymer comprises 100mol.% of the repeating unit of formula (V).

[0079] In another embodiment, the intrinsically conductive polymer has repeating thiophene units of the following general formula (VII):

[0080]

[0081] in,

[0082] a and b are as defined above;

[0083] R5 is an optionally substituted C1-C6 straight chain or branched alkyl group (eg, methyl) or a halogen atom (eg, fluorine);

[0084] X is a hydrogen atom, an alkali metal (e.g., Li, Na, or K), NH(R 1 )3, or HNC5H5, where R 1 Each is independently a hydrogen atom or an optionally substituted C1-C6 alkyl group.

[0085] Specific examples of repeating thiophene compounds are described in U.S. Pat. No. 9,718,905 and may include, for example, sodium 3-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-propanesulfonic acid sodium, potassium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, ammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, triethylammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, and combinations thereof. Each of the thiophene monomers exemplified above can be prepared from thieno[3,4-b]-1,4-dioxin-2-methanol and a branched sultone compound according to a known method (for example, Journal of Electroanalytical Chemistry, 443, 217-226 (1998)).

[0086] Intrinsic conductive polymers can be formed by a variety of techniques as will be understood by those skilled in the art. In a specific embodiment, for example, a thiophene compound with general formula (V) or (VII) can be polymerized in the presence of an oxidation catalyst. Derivatives of these monomers, such as dimers or trimers of the above compounds, can also be used. The derivatives can be composed of identical or different monomer units and used in the following forms: pure form, and mixtures with each other, and / or mixtures with monomers. The oxidized or reduced forms of these precursors can also be used. The amount of the oxidation catalyst used in the polymerization reaction is not particularly limited, and the amount of the oxidation catalyst can be in the range of 1 to 50 mole times, more preferably in the range of 1 to 20 mole times, based on the mole number of the thiophene compound used as the input material. The oxidation catalyst can be a transition metal salt, such as an inorganic acid salt or an organic acid salt containing ammonium, sodium, gold, iron (III), copper (II), chromium (VI), cerium (IV), manganese (IV), manganese (VII) or ruthenium (III) cations. Particularly suitable transition metal salts include: halides (e.g., FeCl3 or HAuCl4); other inorganic acid salts (e.g., Fe(ClO4)3, Fe2(SO4)3, (NH4)2S2O8, or Na3Mo 12 PO 40 ); and organic acid salts and inorganic acid salts containing organic groups. Examples of inorganic acid salts having organic groups include: for example, C1 to C 20 Iron (III) salts of alkyl sulfate monoesters (e.g., iron (III) salts of dodecyl sulfate). Similarly, examples of organic acid salts include: for example, C1 to C 20 an iron(III) salt of an alkanesulfonic acid (e.g., methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, butanesulfonic acid, or dodecanesulfonic acid); an iron(III) salt of an aliphatic perfluorosulfonic acid (e.g., trifluoromethanesulfonic acid, perfluorobutanesulfonic acid, or perfluorooctanesulfonic acid); an aliphatic C1 to C 20 carboxylic acid (e.g., 2-ethylhexyl carboxylic acid); an iron (III) salt of an aliphatic perfluorocarboxylic acid (e.g., trifluoroacetic acid or perfluorooctanoic acid); optionally C1 to C 20 Iron (III) salts of alkyl-substituted aromatic sulfonic acids (e.g., benzenesulfonic acid, o-toluenesulfonic acid, p-toluenesulfonic acid or dodecylbenzenesulfonic acid); iron (III) salts of cycloalkanesulfonic acids (e.g., camphorsulfonic acid); etc. Mixtures of these above-mentioned salts can also be used.

[0087] Oxidative polymerization usually occurs in the presence of one or more solvents. Suitable solvents may include, for example, water, glycols (e.g., ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, hexylene glycol, polyethylene glycol, ethoxydiethylene glycol, dipropylene glycol, etc.); glycol ethers (e.g., methyl glycol ether, ethyl glycol ether, isopropyl glycol ether, etc.); alcohols (e.g., methanol, ethanol, n-propanol, isopropanol, and butanol); ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate, methoxypropyl acetate, ethylene carbonate, propylene carbonate, etc.); amides (e.g., dimethylformamide, dimethylacetamide, dimethyloctyl / decyl fatty acid amide, and N-alkylpyrrolidone); sulfoxides or sulfones (e.g., dimethyl sulfoxide (DMSO) and cyclopentane); phenolic compounds (e.g., toluene, xylene, etc.); and the like. Water is a particularly suitable solvent for the reaction. The amount of solvent used in the polymerization reaction is not particularly limited as long as the thiophene compound used as a material is dissolved in the solvent, but the amount of the solvent is preferably 0.1 to 100 times, more preferably 0.1 to 50 times the weight of the thiophene compound input. The temperature at which the reaction occurs typically varies from about -20°C to about 140°C, and in some embodiments varies from about 20°C to about 100°C. When the reaction is completed, any salt impurities can be removed by known purification techniques, such as by washing with a solvent, reprecipitation, centrifugal sedimentation, ultrafiltration, dialysis or ion exchange resin treatment, and combinations thereof.

[0088] Regardless of how the polymer is formed, it is considered to be "intrinsically" conductive because it has a positive charge located on the backbone that is at least partially compensated by anions covalently bound to the polymer. For example, the polymer can have a relatively high specific conductivity, which in the dry state is about 1 Siemens per centimeter ("S / cm") or more, in some embodiments about 10 S / cm or more, in some embodiments about 25 S / cm or more, in some embodiments about 40 S / cm or more, and in some embodiments about 50 to about 500 S / cm. Due to its intrinsic conductivity, the polymer does not require the addition of conventional dopants (e.g., polystyrene sulfonic acid). In fact, the polymer can be substantially free of such dopants. Nevertheless, it should be understood that dopants can be used in certain embodiments of the present invention. However, when utilized, the dopant is typically present in the solid electrolyte in an amount of about 5 wt.% or less, in some embodiments about 2 wt.% or less, and in some embodiments about 1 wt.% or less.

[0089] The polymer is also generally highly soluble in water, which enables it to be applied to the anode more easily and efficiently. The soluble polymer can also more easily impregnate the small pores formed by the high specific charge powder, so that the resulting solid electrolyte has a "film-like" configuration and coats at least a portion of the anode in a substantially uniform manner. This improves the quality of the resulting oxide and its surface coverage, thereby enhancing the electrical performance of the capacitor.

[0090] The specific mode of incorporating the above-mentioned materials into the pre-coating layer can be changed as needed. For example, in one embodiment, the pre-coating layer can include one or more layers including an organometallic compound, such as described above. In order to apply such a layer, the organometallic compound can be dissolved in an organic solvent and applied to the parts as a solution, such as by screen printing, immersion, electrophoretic coating, spraying, etc. The organic solvent can vary, but is typically an alcohol, such as methanol, ethanol, etc. The organometallic compound can constitute about 0.1wt.% to about 10wt.% of the solution, about 0.2wt.% to about 8wt.% in some embodiments, and about 0.5wt.% to about 5wt.% in some embodiments. Similarly, the solvent can constitute about 90wt.% to about 99.9wt.% of the solution, about 92wt.% to about 99.8wt.% in some embodiments, and about 95wt.% to about 99.5wt.% in some embodiments. Once applied, the parts can be dried to remove the solvent therefrom and form a pre-coating layer including the organometallic compound.

[0091] In another embodiment, the pre-coat layer may include one or more layers comprising an intrinsic conductive polymer, such as described above. Such a layer may be applied in the form of a solution comprising a solvent. The concentration of the polymer may vary according to the desired viscosity and the specific manner in which the layer is applied to the anode. However, typically, the polymer constitutes about 0.1wt.% to about 10wt.% of the solution, about 0.4wt.% to about 5wt.% in some embodiments, and about 0.5wt.% to about 4wt.% in some embodiments. Similarly, the solvent may constitute about 90wt.% to about 99.9wt.% of the solution, about 95wt.% to about 99.6wt.% in some embodiments, and about 96wt.% to about 99.5wt.% in some embodiments. Although other solvents may certainly be used, it is generally desirable that water is the primary solvent so that the solution is considered to be an "aqueous" solution. For example, in most embodiments, water constitutes at least about 50wt.% of the solvent employed, at least about 75wt.% in some embodiments, and about 90wt.% to 100wt.% in some embodiments. When employed, the solution can be applied to the anode using any known technique, such as dipping, casting (e.g., curtain coating, spin coating, etc.), printing (e.g., gravure printing, offset printing, screen printing, etc.), etc. After the resulting conductive polymer layer is applied to the anode, the conductive polymer can be dried and / or washed.

[0092] If desired, the pre-coating layer may also include a combination of an organometallic compound and an intrinsically conductive polymer. These materials may be blended together in a monolayer, or alternatively applied in the form of a separate layer. For example, in one embodiment, the pre-coating layer may include one or more first layers and one or more second layers, the first layer being coated on top of the dielectric, the second layer being coated on top of the first layer. For example, the first layer may include an organometallic compound, and the second layer may include an intrinsically conductive polymer. Alternatively, the first layer may include an intrinsically conductive polymer, and the second layer may include an organometallic compound.

[0093] D. Solid Electrolyte

[0094] The solid electrolyte overlies the pre-coating layer and generally functions as the cathode of the capacitor. Typically, the total thickness of the solid electrolyte is from about 1 to about 50 μm, and in some embodiments from about 5 to about 20 μm. As described above, the solid electrolyte comprises a conductive polymer having repeating units derived from an aniline monomer having the following general formula (I):

[0095]

[0096] in,

[0097] R5 and R6 are independently hydrogen, alkyl (e.g., methyl, ethyl, hexyl, octyl, etc.), alkenyl, aryl, alkoxy (e.g., methoxy, ethoxy, etc.), aryloxy (e.g., phenoxy), alkylthioalkyl, alkaryl, aralkyl, halogenated alkyl (e.g., trifluoromethyl), amino, epoxy, silane, siloxane, alcohol, benzyl, carboxylate, ether, ether carboxylate, ether sulfonate, ester sulfonate, carbamate, etc., or a combination thereof. For example, in a particular embodiment, R5 and R6 are hydrogen, such that the conductive polymer comprises repeating units derived from aniline. In other embodiments, one or both of R5 or R6 may be alkyl (e.g., methyl) or alkoxy (e.g., methoxy). Typically, polyaniline has a weight average molecular weight of about 20,000 g per mole or more, in some embodiments, about 50,000 to 500,000 g per mole, and in some embodiments, about 60,000 to about 300,000 g per mole, as determined, for example, by polystyrene conversion as measured by gel permeation chromatography.

[0098] Aniline polymers derived from monomers of formula (I) are generally considered to be "non-intrinsic" conductive because they typically require the presence of a dopant. For example, in certain embodiments, aniline monomers can be polymerized in a composition that also includes a proton donor, which can therefore be used as an internal dopant for the polymer. The amount of such proton donors typically employed is from about 0.1 to about 0.5 moles per mole of aniline monomer, from about 0.3 to about 0.45 moles per mole of aniline monomer in some embodiments, and from about 0.3 to about 0.4 moles per mole of aniline monomer in some embodiments. Suitable proton donors may include, for example, Bronsted acids or salts thereof, particularly organic acids and / or salts thereof. For example, in one embodiment, the proton donor may be an organic acid compound, such as those having the following general formula (VIII):

[0099]

[0100] in,

[0101] m is an integer from 1 to 10 (e.g., 1 or 2);

[0102] M is: hydrogen; organic free radicals, such as aromatic compounds (e.g., pyridinium, imidazolium, anilinium, etc.); inorganic free radicals, such as alkali metals (e.g., lithium, sodium, potassium, etc.), alkaline earth metals (e.g., calcium, magnesium, etc.), transition metals (e.g., iron), ammonium, etc.; etc.;

[0103] X is an anion, such as SO3 - PO3 2- PO4(OH)- 、OPO3 2- 、OPO2(OH) - 、COO - wait;

[0104] R 4 , R 5 and R 6 independently: hydrogen; a hydrocarbon group, such as a straight or branched C1-C 24 alkyl (e.g., octyl or 2-ethylhexyl), cycloalkyl, aryl (e.g., pentyl), alkaryl, etc.; or R 9 3Si-group, where R 9 are each independently hydrogen or a hydrocarbyl group; and

[0105] R 7 and R 8 Independently: a hydrocarbon group, such as a straight or branched C1-C 24 alkyl (e.g., butyl, octyl, decyl or 2-ethylhexyl), cycloalkyl, aryl (e.g., pentyl), alkaryl, etc.; or -(R 10 O) q -R 11 , wherein q is an integer equal to or greater than 1 (e.g., 1 to 10), R 10 is a hydrocarbon group or a silylene group, R 11 is hydrogen, a hydrocarbon group or R 12 3Si-, where R 12 Each is independently a hydrocarbon group.

[0106] For example, in one particular embodiment, X can be SO3, R 4 can be hydrogen, R 5 may be hydrogen, and / or R 6 In such an embodiment, for example, R 7 and / or R 8 It can be a straight chain or branched C1-C 24 Alkyl, for example butyl, octyl, decyl or 2-ethylhexyl. For example, a particularly suitable proton donor is sodium di-2-ethylhexyl sulfosuccinate.

[0107] As will be appreciated by those skilled in the art, conductive polymers can be formed by a variety of techniques. For example, in a specific embodiment, polyaniline derived from general formula (I) can be polymerized in a composition comprising an oxidation catalyst. Derivatives of these monomers can also be used, such as dimers or trimers of the above compounds. The derivative can be composed of identical or different monomer units, and is used in the following form: pure form, and mixtures with each other, and / or mixtures with monomers. Oxidized forms or reduced forms of these precursors can also be used. The amount of the oxidation catalyst used in the polymerization reaction is not particularly limited, and in the molar number of the aniline monomer used as input material, the amount of the oxidation catalyst can be in the range of 1 to 50 mole times, more preferably 1 to 20 mole times. The oxidation catalyst can be a transition metal salt, such as described above.

[0108] In addition to monomers and other optional components (eg, proton donors, catalysts, etc.), the polymerization composition typically includes one or more solvents, such as described in US Pat. No. 9,754,697, which is incorporated herein by reference in its entirety. Suitable solvents may include, for example, water, glycols (e.g., ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, hexylene glycol, polyethylene glycol, ethoxydiethylene glycol, dipropylene glycol, etc.); glycol ethers (e.g., methyl glycol ether, ethyl glycol ether, isopropyl glycol ether, etc.); alcohols (e.g., methanol, ethanol, n-propanol, isopropanol, and butanol); ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate, methoxypropyl acetate, ethylene carbonate, propylene carbonate, etc.); amides (e.g., dimethylformamide, dimethylacetamide, dimethyl octanyl / decyl fatty acid amide, and N-alkylpyrrolidone); sulfoxides or sulfones (e.g., dimethyl sulfoxide (DMSO) and sulfolane); phenolic compounds (e.g., toluene, xylene, etc.); etc. In some cases, a variety of solvents may be used, such as water and an organic solvent (e.g., toluene). The amount of the solvent used in the polymerization reaction is not particularly limited, as long as the aniline monomer used as a material is dissolved in the solvent, but the amount of the solvent is preferably 0.1 to 100 times, more preferably 0.1 to 50 times the weight of the aniline monomer input. The temperature at which the reaction occurs typically varies from about -20°C to about 140°C, and in some embodiments varies from about 20°C to about 100°C. When the reaction is completed, any salt impurities can be removed by known purification techniques, such as by washing with a solvent, reprecipitation, centrifugal sedimentation, ultrafiltration, dialysis or ion exchange resin treatment, and combinations thereof.

[0109] Of course, other components can also be used in the polymeric composition to enhance the performance of the resulting solid electrolyte. For example, in some embodiments, an inorganic acid (e.g., phosphoric acid) can be used. Similarly, an emulsifier can be used to help minimize the risk of phase inversion during polymerization. Suitable emulsifiers can include, for example, ionic emulsifiers and nonionic emulsifiers known in the art.

[0110] As mentioned above, aniline polymers derived from monomers of formula (I) are generally considered to be "non-intrinsic" conductive because they typically require the presence of a dopant. In addition to the internal dopant discussed above or in place of the internal dopant discussed above, an external dopant can also be used in the solid electrolyte, which forms a complex or composite with the polyaniline after the polyaniline is formed. An embodiment of such an external dopant is a phenolic compound. When adopted, the amount of such a phenolic compound is typically the following amount: about 10 to about 60 grams per gram of polyaniline, about 15 to about 50 grams per gram of polyaniline in some embodiments, and about 20 to about 40 grams per gram of polyaniline in some embodiments. Suitable phenolic compounds can include hydroxyphenolic compounds, such as those having one of the following structures (IX), (X), (XI) or (XII):

[0111]

[0112] in,

[0113] n is an integer from 0 to 5, preferably an integer from 0 to 3 (eg, 0 or 1); and

[0114] R is independently C1-C 20 Alkyl, alkenyl, cycloalkyl, aryl, alkaryl, etc.

[0115] Specific embodiments of the hydroxyphenolic compounds of formula (IX) may include methoxyphenol, ethoxyphenol, propoxyphenol, isopropoxyphenol, butoxyphenol, isobutoxyphenol and tert-butoxyphenol. Specific embodiments of the hydroxyphenolic compounds of formula (X) may include hydroxynaphthalene. Specific embodiments of the hydroxyphenolic compounds of formula (XI) may include cresol, ethylphenol, propylphenol (e.g., 4-isopropylphenol), butylphenol and amylphenol (e.g., 4-tert-amylphenol). Similarly, specific embodiments of the hydroxyphenolic compounds of formula (XII) may include 1,6-naphthanediol, 2,6-naphthalenediol and 2,7-naphthalenediol.

[0116] If desired, a thermal stabilizer may also be employed in the solid electrolyte. When employed, such thermal stabilizers are typically employed in an amount of about 10 to about 60 grams per gram of polyaniline, in some embodiments about 15 to about 50 grams per gram of polyaniline, and in some embodiments about 20 to about 40 grams per gram of polyaniline. Suitable thermal stabilizers include, for example, organic acids, inorganic acids, and / or salts thereof. For example, suitable heat stabilizers may include: organic sulfonic acids, such as alkyl sulfonic acids (e.g., methanesulfonic acid, ethanesulfonic acid, di-2-ethylhexylsulfosuccinic acid, etc.) and aromatic sulfonic acids (e.g., benzenesulfonic acid, naphthalenesulfonic acid, anthracenesulfonic acid, dodecylbenzenesulfonic acid, anthraquinonesulfonic acid, etc.); organic carboxylic acids, such as alkyl carboxylic acids (e.g., undecylenic acid, cyclohexanecarboxylic acid, 2-ethylhexanoic acid, etc.) and aromatic carboxylic acids (e.g., salicylic acid, benzoic acid, naphthoic acid, trimesic acid, etc.); organic phosphoric acids, such as alkyl phosphoric acids (e.g., dodecylphosphoric acid, bis(2-ethylhexyl) hydrogen phosphate, etc.) and aromatic phosphoric acids; organic phosphonic acids, such as alkyl phosphonic acids and aromatic phosphonic acids (e.g., phenylphosphonic acid, naphthylphosphonic acid, phenylphosphonic acid, etc.); and the like, and salts of any of the foregoing.

[0117] The resulting polyaniline can easily impregnate the small pores formed by the high specific charge powder, so that the resulting solid electrolyte has a "film-like" configuration and coats at least a portion of the anode in a substantially uniform manner. This improves the quality of the resulting oxide and its surface coverage, thereby enhancing the electrical performance of the capacitor.

[0118] i. Inner layer

[0119] Solid electrolytes are typically formed by one or more "inner" conductive polymer layers. In this context, the term "inner" refers to one or more layers formed by the same material and (directly or via another layer (e.g., an adhesive layer)) coated on top of the dielectric. For example, the inner layer typically comprises polyaniline such as described above. In a specific embodiment, the inner layer is typically free of other types of conductive polymers, and is therefore primarily formed by polyaniline as described herein. More particularly, polyaniline can constitute about 50wt.% or more of the inner layer, about 70wt.% or more in some embodiments, and about 90wt.% or more (e.g., 100wt.%) in some embodiments. One or more inner layers can be used. For example, a solid electrolyte typically comprises 2 to 30 inner layers, 4 to 20 inner layers in some embodiments, and about 5 to 15 inner layers (e.g., 10 layers) in some embodiments.

[0120] The inner layer can be applied in the form of a solution comprising a solvent. The concentration of polyaniline can vary according to the desired viscosity and the specific mode in which the layer is applied to the anode. However, typically, polyaniline constitutes about 0.1 to about 10wt.% of the solution, about 0.4 to about 5wt.% in some embodiments, and about 0.5 to about 4wt.% in some embodiments. Similarly, the solvent can constitute about 90wt.% to about 99.9wt.% of the solution, about 95wt.% to about 99.6wt.% in some embodiments, and about 96wt.% to about 99.5wt.% in some embodiments. When adopted, the solution can be applied to the anode using any known technology, such as immersion, casting (e.g., curtain coating, spin coating, etc.), printing (e.g., gravure printing, offset printing, screen printing, etc.), etc. After the resulting conductive polymer layer is applied to the anode, the resulting conductive polymer layer can be dried and / or washed.

[0121] ii. Outer layer

[0122] The solid electrolyte may comprise only an "inner layer" such that it is substantially formed of the same material (i.e., polyaniline). Nevertheless, in other embodiments, the solid electrolyte may also comprise one or more optional "outer" conductive polymer layers, which are formed of a material different from the inner layer and are coated on top of the inner layer. For example, the outer layer may be formed of other types of polyaniline or other types of conductive polymers (e.g., polypyrrole, polythiophene, etc.). In a particular embodiment, the outer layer is primarily formed of such a non-intrinsic conductive polymer, wherein the non-intrinsic conductive polymer constitutes about 50 wt.% or more of the corresponding outer layer, in some embodiments about 70 wt.% or more, and in some embodiments about 90 wt.% or more (e.g., 100 wt.%). One or more outer layers may be employed. For example, the solid electrolyte may comprise 2 to 30 outer layers, in some embodiments 4 to 20 outer layers, and in some embodiments about 5 to 15 outer layers.

[0123] When employed, the outer layer may, for example, comprise a thiophene polymer having repeating units of the following formula (XIII):

[0124]

[0125] in,

[0126] R7 is: a linear or branched C1 to C 18Alkyl groups (e.g., methyl, ethyl, n-propyl or isopropyl, n-butyl, isobutyl, sec-butyl or tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, etc.); C5 to C 12 Cycloalkyl groups (e.g., cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, etc.); C6 to C 14 Aryl group (eg, phenyl, naphthyl, etc.); C7 to C 18 an aralkyl group (e.g., benzyl, o-tolyl, m-tolyl, p-tolyl, 2,3-xylyl, 2,4-xylyl, 2,5-xylyl, 2-6-xylyl, 3-4-xylyl, 3,5-xylyl, mesityl, etc.); a C1 to C4 hydroxyalkyl group, or a hydroxyl group; and

[0127] q is an integer from 0 to 8, in some embodiments from 0 to 2, and in one embodiment is 0. In one specific embodiment, "q" is 0 and the polymer is poly(3,4-ethylenedioxythiophene). A commercially suitable example of a monomer suitable for forming such a polymer is 3,4-ethylenedioxythiophene, which is available from Heraeus under the name Clevios TM M obtained.

[0128] The polymers of formula (XIII) are generally considered to be "extrinsic" conductive, so that these polymers require the presence of a separate counterion that is not covalently bound to the polymer. The counterion can be a monomeric anion or a polymeric anion that offsets the charge of the conductive polymer. The polymeric anion can be, for example, an anion of a polymeric carboxylic acid (e.g., polyacrylic acid, polymethacrylic acid, polymaleic acid, etc.); a polymeric sulfonic acid (e.g., polystyrene sulfonic acid ("PSS"), polyvinyl sulfonic acid, etc.); and the like. The acid can also be a copolymer, such as a copolymer of vinyl carboxylic acid and vinyl sulfonic acid with other polymerizable monomers (e.g., acrylates and styrene). Similarly, suitable monomeric anions include, for example, anions of: C1 to C 20 Alkane sulfonic acid (e.g., dodecane sulfonic acid); aliphatic perfluorosulfonic acid (e.g., trifluoromethane sulfonic acid, perfluorobutane sulfonic acid, or perfluorooctane sulfonic acid); aliphatic C1 to C 20 carboxylic acid (e.g., 2-ethyl-hexyl carboxylic acid); aliphatic perfluorocarboxylic acid (e.g., trifluoroacetic acid or perfluorooctanoic acid); optionally C1 to C 20Alkyl substituted aromatic sulfonic acids (e.g., benzenesulfonic acid, o-toluenesulfonic acid, p-toluenesulfonic acid, or dodecylbenzenesulfonic acid); cycloalkanesulfonic acids (e.g., camphorsulfonic acid or tetrafluoroborate, hexafluorophosphate, perchlorate, hexafluoroantimonate, hexafluoroarsenate, or hexachloroantimonate); and the like. Particularly suitable counter anions are polymeric anions, such as polymeric carboxylic acids or sulfonic acids (e.g., polystyrenesulfonic acid ("PSS")). The molecular weight of such polymeric anions typically ranges from about 1,000 to about 2,000,000, and in some embodiments from about 2,000 to about 500,000.

[0129] When adopted, it may be desirable that the non-intrinsic conductive polymer is applied in the form of a dispersion of prepolymerized conductive particles. Typically, such particles have an average size (e.g., diameter) of about 1 to about 100 nanometers, in some embodiments about 2 to about 80 nanometers, and in some embodiments about 4 to about 50 nanometers. The diameter of the particles can be determined using known techniques, such as by ultracentrifugation, laser diffraction, etc. Similarly, the shape of the particles can vary. For example, in a particular embodiment, the particles are spherical. However, it should be understood that the present invention also contemplates other shapes, such as plates, rods, discs, strips, tubes, irregular shapes, etc. The concentration of the particles in the dispersion can vary according to the desired viscosity of the dispersion and the specific manner in which the dispersion is to be applied to the capacitor element. However, typically, the particles constitute about 0.1 to about 10wt.%, in some embodiments about 0.4 to about 5wt.%, and in some embodiments about 0.5 to about 4wt.%.

[0130] Dispersion can also comprise one or more tackiness agents, to further strengthen the bonding properties of polymer layer and also increase the stability of particles in dispersion.Tackiness agent can be organic in nature, for example polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl chloride, polyvinyl acetate, polyvinyl butyrate, polyacrylate, polyacrylamide, polymethacrylate, polymethacrylamide, polyacrylonitrile, styrene / acrylate, vinyl acetate / acrylate and ethylene / vinyl acetate copolymer, polybutadiene, polyisoprene, polystyrene, polyether, polyester, polycarbonate, polyurethane, polyamide, polyimide, polysulfone, melamine formaldehyde resin, epoxy resin, silicone resin or cellulose.Crosslinking agent can also be adopted to strengthen the bonding ability of tackiness agent. Such crosslinking agents may include, for example, melamine compounds, masked isocyanates or functionalized silanes (e.g., 3-glycidoxypropyltrialkoxysilane, tetraethoxysilane and tetraethoxysilane hydrolyzate), or crosslinkable polymers (e.g., polyurethanes, polyacrylates or polyolefins), and subsequent crosslinking.

[0131] Dispersants can also be used to facilitate the ability to apply the layer to the anode. Suitable dispersants include solvents such as aliphatic alcohols (e.g., methanol, ethanol, isopropanol and butanol), aliphatic ketones (e.g., acetone and methyl ethyl ketone), aliphatic carboxylates (e.g., ethyl acetate and butyl acetate), aromatic hydrocarbons (e.g., toluene and xylene), aliphatic hydrocarbons (e.g., hexane, heptane and cyclohexane), chlorinated hydrocarbons (e.g., methylene chloride and ethylene dichloride), aliphatic nitriles (e.g., acetonitrile), aliphatic sulfoxides and sulfones (e.g., dimethyl sulfoxide and cyclopentane), aliphatic carboxylic acid amides (e.g., methylacetamide, dimethylacetamide and dimethylformamide), aliphatic and araliphatic ethers (e.g., diethyl ether and anisole), water, and mixtures of any of the foregoing solvents. A particularly suitable dispersant is water.

[0132] In addition to those mentioned above, other ingredients can also be used in the dispersion. For example, a conventional filler can be used, the size of which is from about 10 nanometers to about 100 microns, from about 50 nanometers to about 50 microns in some embodiments, and from about 100 nanometers to about 30 microns in some embodiments. Examples of such fillers include calcium carbonate, silicates, silicon oxide, calcium sulfate or barium sulfate, aluminum hydroxide, glass fibers or bulbs, wood flour, cellulose powder carbon black, conductive polymers, etc. The filler can be introduced into the dispersion in powder form, but can also exist in other forms (e.g., fibers).

[0133] Surface active substances such as ionic or nonionic surfactants may also be used in the dispersion. In addition, binders such as organofunctional silanes or hydrolyzates thereof such as 3-glycidyloxypropyltrialkoxysilane, 3-aminopropyl-triethoxysilane, 3-mercaptopropyl-trimethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane or octyltriethoxysilane may be used. The dispersion may also contain additives that increase the electrical conductivity such as compounds containing ether groups (e.g., tetrahydrofuran), compounds containing lactone groups (e.g., γ-butyrolactone or γ-valerolactone), compounds containing amide groups or lactam groups (e.g., caprolactam, N-methylcaprolactam, N,N-dimethylacetamide, N-methylacetamide, N,N-dimethylformamide (DMF), N-methylformamide, N-methylformanilide, N-methylpyrrolidone) may be used. (N-methylpyrrolidone, NMP), N-octylpyrrolidone or pyrrolidone), sulfones and sulfoxides (e.g., sulfolane (tetramethylene sulfone) or dimethylsulfoxide (DMSO)), sugars or sugar derivatives (e.g., sucrose, glucose, fructose or lactose), sugar alcohols (e.g., sorbitol or mannitol), furan derivatives (e.g., 2-furancarboxylic acid or 3-furancarboxylic acid), alcohols (e.g., ethylene glycol, glycerol, diethylene glycol or triethylene glycol).

[0134] The dispersion can be applied using various known techniques, for example by spin coating, dipping, pouring, dropwise application, injection, spraying, doctor blading, brushing, printing (e.g., inkjet printing, screen printing, or pad printing), or immersion. The viscosity of the dispersion is typically from about 0.1 to about 100,000 mPas (at 100 s -1 In some embodiments, the shear rate is about 1 to about 10,000 mPas, in some embodiments, about 10 to about 1,500 mPas, and in some embodiments, about 100 to about 1000 mPas.

[0135] If desired, hydroxyl-functionalized nonionic polymers may also be employed in the outer layer of the solid electrolyte. The term "hydroxyl-functionalized" generally means that the compound contains at least one hydroxyl functional group or is capable of having such a functional group in the presence of a solvent. Without intending to be limited by theory, it is believed that the use of hydroxyl-functionalized polymers having a certain molecular weight can minimize the possibility of chemical decomposition under high voltage. For example, the molecular weight of the hydroxyl-functionalized polymer can be about 100 to 10,000 g per mole, about 200 to 2,000 in some embodiments, about 300 to about 1,200 in some embodiments, and about 400 to about 800 in some embodiments.

[0136] For this purpose, any of the various hydroxyl-functionalized nonionic polymers can be used generally. For example, in one embodiment, the hydroxyl-functionalized polymer is a polyalkylene ether. The polyalkylene ether can include polyalkylene glycols (for example, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyepichlorohydrin, etc.), polyoxetane, polyphenylene oxide, polyether ketone, etc. Typically, the polyalkylene ether is mainly a straight chain nonionic polymer with terminal hydroxyl groups. Particularly suitable are polyethylene glycol, polypropylene glycol and polytetramethylene glycol (polytetrahydrofuran), which are prepared by addition polymerization of ethylene oxide, propylene oxide or tetrahydrofuran to water. The polyalkylene ether can be prepared by diols or polyols by polycondensation reaction. In particular, the diol component can be selected from: saturated or unsaturated, branched or unbranched aliphatic dihydroxy compounds containing 5 to 36 carbon atoms; or saturated or unsaturated, branched or unbranched aromatic dihydroxy compounds, for example, pentane-1,5-diol, hexane-1,6-diol, neopentyl glycol, bis-(hydroxymethyl)-cyclohexane, bisphenol A, dimer diol, hydrogenated dimer diol, or even mixtures of the mentioned diols. In addition, polyhydric alcohols can also be used in the polymerization reaction, for example, including glycerol, diglycerol and polyglycerol, trimethylolpropane, pentaerythritol or sorbitol.

[0137] In addition to those mentioned above, other hydroxyl-functionalized nonionic polymers may also be used in the present invention. Some examples of such polymers include: for example, ethoxylated alkylphenols; ethoxylated C6-C 24 Fatty alcohol or propoxylated C6-C 24 Fatty alcohol; having the general formula CH3-(CH2) 10-16 -(O-C2H4) 1-25 -OH-containing polyethylene glycol alkyl ethers (e.g., octaethylene glycol monododecyl ether and pentaethylene glycol monododecyl ether); having the general formula CH3-(CH2) 10-16 -(O-C3H6) 1-25 -OH polyoxypropylene glycol alkyl ether; having the following general formula: C8H 17 -(C6H4)-(O-C2H4) 1-25 -OH polyoxyethylene glycol octylphenol ether (for example, Triton TM X-100); having the following general formula: C9H 19 -(C6H4)-(O-C2H4) 1-25 -OH polyoxyethylene glycol alkylphenol ether (e.g., nonoxynol-9); C8-C 24Polyoxyethylene glycol esters of fatty acids, such as polyoxyethylene glycol sorbitan alkyl esters (e.g., polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene (20) sorbitan monopalmitate, polyoxyethylene (20) sorbitan monostearate, polyoxyethylene (20) sorbitan monooleate, PEG-20 methyl glucose distearate, PEG-20 methyl glucose sesquistearate, PEG-80 castor oil, and PEG-20 castor oil, PEG-3 castor oil, PEG 600 dioleate, and PEG 400 dioleate) and polyoxyethylene glycerol alkyl esters (e.g., polyoxyethylene-23 glyceryl laurate and polyoxyethylene-20 glyceryl stearate); C8-C 24 Polyoxyethylene glycol ethers of fatty acids (e.g., polyoxyethylene-10 cetyl ether, polyoxyethylene-10 stearyl ether, polyoxyethylene-20 cetyl ether, polyoxyethylene-10 oleyl ether, polyoxyethylene-20 oleyl ether, polyoxyethylene-20 isocetyl ether, polyoxyethylene-15 tridecyl ether, and polyoxyethylene-6 tridecyl ether); block copolymers of polyethylene glycol and polypropylene glycol (e.g., Poloxamers); and the like, and mixtures thereof.

[0138] Hydroxyl functionalized nonionic polymers can be incorporated into the outer layer in various ways. For example, in certain embodiments, the nonionic polymer can be simply incorporated into a dispersion of a non-intrinsic conductive polymer. In such embodiments, the concentration of the nonionic polymer in the layer can be from about 1wt.% to about 50wt.%, in some embodiments from about 5wt.% to about 40wt.%, and in some embodiments from about 10wt.% to about 30wt.%. However, in other embodiments, the nonionic polymer can be applied after the initial outer layer is formed. In such embodiments, the technology for applying the nonionic polymer can vary. For example, the nonionic polymer can be applied in the form of a liquid solution using various methods, such as dipping, immersion, pouring, dripping, injection, spraying, spreading, coating or printing (e.g., inkjet, screen printing or pad printing). In this solution, a solvent known to those skilled in the art can be used, such as water, alcohol or a mixture thereof. In such a solution, the concentration of the nonionic polymer typically ranges from about 5 wt.% to about 95 wt.% of the solution, in some embodiments, from about 10 wt.% to about 70 wt.%, and in some embodiments, from about 15 wt.% to about 50 wt.%. If desired, such a solution may generally be free of a conductive polymer. For example, a conductive polymer may constitute about 2 wt.% or less of the solution, in some embodiments, about 1 wt.% or less, and in some embodiments, about 0.5 wt.% or less.

[0139] E. External polymer coating

[0140] If desired, an external polymer coating may also be applied to anode, which is coated on top of a solid electrolyte. External polymer coatings typically include one or more layers formed by conductive polymer particles, such as described above (e.g., formed by non-intrinsic conductive polymers). External coatings may be able to further penetrate into the edge region of a capacitor body (main body, body), thereby increasing the adhesion to dielectric and producing more mechanically robust (robust) parts, which can reduce equivalent series resistance and leakage current. Because it is generally intended to improve edge coverage rather than the inside of an impregnated anode body, the particles used in the external coatings typically have larger sizes than those sizes used in any optional particles used in a solid electrolyte (e.g., in an outer layer). For example, the average size of the particles used in the external polymer coatings is typically about 1.5 to about 30, about 2 to about 20 in some embodiments, and about 5 to about 15 in some embodiments. For example, the particles employed in the outer coating may have an average size of about 50 to about 800 nanometers, in some embodiments, about 80 to about 600 nanometers, and in some embodiments, about 100 to about 500 nanometers.

[0141] A crosslinking agent may also be optionally employed in the outer polymer coating to further enhance the degree of adhesion to the solid electrolyte. Typically, the crosslinking agent is applied prior to applying the dispersion used in the outer coating. For example, a suitable crosslinking agent is Merker et al. The amines are described in U.S. Patent Publication No. 2007 / 0064376 and include, for example, amines (e.g., diamines, triamines, oligoamines, polyamines, etc.); polyvalent metal cations, such as salts or compounds of Mg, Al, Ca, Fe, Cr, Mn, Ba, Ti, Co, Ni, Cu, Ru, Ce, or Zn, phosphonium compounds, sulfonium compounds, etc. Particularly suitable examples include, for example, 1,4-diaminocyclohexane, 1,4-bis(amino-methyl)cyclohexane, ethylenediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,12-dodecanediamine, N,N-dimethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-1,4-butanediamine, etc., and mixtures thereof.

[0142] The crosslinking agent is typically applied by a solution or dispersion having a pH of 1 to 10, in some embodiments 2 to 7, and in some embodiments 3 to 6, as determined at 25°C. Acidic compounds can be used to help achieve the desired pH level. Examples of solvents or dispersants for crosslinking agents include water or organic solvents, such as alcohols, ketones, carboxylates, and the like. The crosslinking agent can be applied to the capacitor body by any known process, such as spin coating, dipping, casting, dropwise application, spray application, vapor deposition, sputtering, sublimation, scraping, brushing or printing (e.g., inkjet, screen printing or pad printing). Once applied, the crosslinking agent can be dried before applying the polymer dispersion. The process can then be repeated until the desired thickness is obtained. For example, the total thickness of the entire outer polymer coating (including the crosslinking agent and the dispersion layer) can range from about 1 to about 50 μm, in some embodiments from about 2 to about 40 μm, and in some embodiments from about 5 to about 20 μm.

[0143] F. Cathodic Coating

[0144] If desired, the capacitor element can also be coated with a cathode coating on top of the solid electrolyte and the outer polymer coating. The cathode coating can include a metal particle layer, which includes a plurality of conductive metal particles dispersed in a polymer matrix. The particles typically constitute about 50wt.% to about 99wt.% of the layer, in some embodiments about 60wt.% to about 98wt.%, and in some embodiments about 70wt.% to about 95wt.%, while the polymer matrix typically constitutes about 1wt.% to about 50wt.% of the layer, in some embodiments about 2wt.% to about 40wt.%, and in some embodiments about 5wt.% to about 30wt.%.

[0145] Conductive metal particles can be formed from a variety of different metals (e.g., copper, nickel, silver, nickel, zinc, tin, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium, etc., and alloys thereof). Silver is a particularly suitable conductive metal for use in this layer. The metal particles are generally of relatively small size, such as an average size of about 0.01 to about 50 microns, in some embodiments about 0.1 to about 40 microns, and in some embodiments about 1 to about 30 microns. Typically, only one metal particle layer is used, however, it should be understood that multiple layers may be used if desired. The total thickness of such a layer typically ranges from about 1 μm to about 500 μm, in some embodiments about 5 μm to about 200 μm, and in some embodiments about 10 μm to about 100 μm.

[0146] The polymer matrix typically includes a polymer that can be thermoplastic or thermosetting in nature. However, typically, the polymer is selected so that the polymer can be used as a barrier to the electromigration of silver ions, and the polymer is also made to contain a relatively small amount of polar groups, thereby minimizing the water adsorption degree in the cathode coating. In this regard, the inventors have found that vinyl acetal polymers (e.g., polyvinyl butyral, polyvinyl formal, etc.) are particularly suitable for this purpose. For example, polyvinyl butyral can be formed by reacting polyvinyl alcohol with an aldehyde (e.g., butyraldehyde). Because the reaction is typically incomplete, polyvinyl butyral will generally have a residual hydroxyl content. However, by minimizing the content, the polymer can have a small degree of strong polar groups, otherwise the strong polar groups can cause a high degree of moisture adsorption and cause silver ion migration. For example, the residual hydroxyl content in the polyvinyl acetal can be about 35mol.% or less, about 30mol.% or less in some embodiments, and about 10mol.% to about 25mol.% in some embodiments. One commercially available example of such a polymer is available from Sekisui Chemical Co., Ltd under the name "BH-S" (polyvinyl butyral).

[0147] To form the cathode coating, a conductive paste is typically applied to the capacitor overlying a solid electrolyte. One or more organic solvents are typically employed in the paste. Generally, various organic solvents can be used, such as glycols (e.g., propylene glycol, butylene glycol, triethylene glycol, hexylene glycol, polyethylene glycol, ethoxydiethylene glycol and dipropylene glycol); glycol ethers (e.g., methyl glycol ether, ethyl glycol ether and isopropyl glycol ether); ethers (e.g., diethyl ether and tetrahydrofuran); alcohols (e.g., benzyl alcohol, methanol, ethanol, n-propanol, isopropanol and butanol); triglycerides; ketones (e.g., acetone, methyl ethyl ketone and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate and methoxypropyl acetate); amides (e.g., dimethylformamide, dimethylacetamide, dimethyl octanyl / decyl fatty acid amide and N-alkylpyrrolidone); nitriles (e.g., acetonitrile, propionitrile, butyronitrile and benzonitrile); sulfoxides or sulfones (e.g., dimethyl sulfoxide (DMSO) and sulfolane); etc., and mixtures thereof. The organic solvent typically constitutes about 10 wt.% to about 70 wt.%, in some embodiments, about 20 wt.% to about 65 wt.%, and in some embodiments, about 30 wt.% to about 60 wt.%. Typically, the metal particles constitute about 10 wt.% to about 60 wt.%, in some embodiments, about 20 wt.% to about 45 wt.%, and in some embodiments, about 25 wt.% to about 40 wt.%, and the resinous matrix constitutes about 0.1 wt.% to about 20 wt.%, in some embodiments, about 0.2 wt.% to about 10 wt.%, and in some embodiments, about 0.5 wt.% to about 8 wt.% of the paste.

[0148] The paste can have a relatively low viscosity, making it easy to handle and apply to capacitor elements. For example, the viscosity can range from about 50 to about 3,000 centipoise, in some embodiments from about 100 to about 2,000 centipoise, and in some embodiments from about 200 to about 1,000 centipoise, such as measured by a Brookfield Dv-1 viscometer (cone and plate) running at a speed of 10 rpm and a temperature of 25°C. If necessary, a thickener or other viscosity modifier can be used in the paste to increase or reduce the viscosity. In addition, the thickness of the applied paste can also be relatively thin and still achieve the desired performance. For example, the thickness of the paste can be from about 0.01 to about 50 microns, in some embodiments from about 0.5 to about 30 microns, and in some embodiments from about 1 to about 25 microns. Once applied, the metal paste can be optionally dried to remove certain components, such as organic solvents. For example, drying may occur at a temperature of about 20°C to about 150°C, in some embodiments, about 50°C to about 140°C, and in some embodiments, about 80°C to about 130°C.

[0149] G. Other components

[0150] If desired, the capacitor may also include other layers known in the art. In certain embodiments, for example, a carbon layer (e.g., graphite) may be positioned between the solid electrolyte and the silver layer, which may help further limit the contact of the silver layer with the solid electrolyte. In addition, a pre-coating layer may also be used, which is overlying the dielectric and includes an organometallic compound.

[0151] II.Terminal

[0152] Once formed, the capacitor element can be provided with a terminal, especially when used in surface mounting applications. For example, the capacitor can include an anode terminal electrically connected to the anode lead of the capacitor element and a cathode terminal electrically connected to the cathode of the capacitor element. Any conductive material can be used to form the terminal, such as a conductive metal (for example, copper, nickel, silver, nickel, zinc, tin, palladium, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium and their alloys). Particularly suitable conductive metals include, for example, copper, copper alloys (for example, copper-zirconium, copper-magnesium, copper-zinc or copper-iron), nickel and nickel alloys (for example, nickel-iron). The thickness of the terminal is usually selected to minimize the thickness of the capacitor. For example, the thickness of the terminal can range from about 0.05 to about 1 mm, about 0.05 to about 0.5 mm in some embodiments, and about 0.07 to about 0.2 mm. An exemplary conductive material is a copper-iron alloy metal plate that can be obtained from Wieland (Wieland, Germany). If necessary, the surface of the terminal can be plated with nickel, silver, gold, tin, etc. as known in the art to ensure that the final component can be mounted to the circuit board. In a specific embodiment, the two surfaces of the terminal are plated with a nickel flash layer and a silver flash layer, respectively, and the mounting surface is also plated with a tin solder layer.

[0153] The terminals may be connected to the capacitor element using any technique known in the art. In one embodiment, for example, a lead frame may be provided that defines a cathode terminal and an anode terminal. In order to attach the electrolytic capacitor element to the lead frame, a conductive adhesive may first be applied to the surface of the cathode terminal. For example, the conductive adhesive may include conductive metal particles contained in a resin composition. The metal particles may be silver, copper, gold, platinum, nickel, zinc, bismuth, and the like. The resin composition may include a thermosetting resin (e.g., an epoxy resin), a curing agent (e.g., anhydride), and a coupling agent (e.g., a silane coupling agent). Suitable conductive adhesives may be present in the form of a conductive adhesive. Osako et al.The conductive adhesive may be applied to the cathode terminal using any of a variety of techniques. For example, printing techniques may be used due to their practical and cost-saving advantages. The anode lead may also be electrically connected to the anode terminal using any technique known in the art (e.g., mechanical welding, laser welding, conductive adhesives, etc.). Once the anode lead is electrically connected to the anode terminal, the conductive adhesive may be cured to ensure that the electrolytic capacitor element is adequately bonded to the cathode terminal.

[0154] III. Housing

[0155] The capacitor element can be incorporated into the housing in various ways. For example, in some embodiments, the capacitor element can be encapsulated in a case, and then the case can be filled with a resin material such as a thermosetting resin (e.g., epoxy resin), which can be cured to form a hardened housing. The resin material can surround and encapsulate the capacitor element so that at least a portion of the anode terminal and the cathode terminal are exposed for installation on a circuit board. When encapsulated in this way, the capacitor element and the resin material form an integrated capacitor.

[0156] Of course, in alternative embodiments, it may be desirable to enclose the capacitor element in a separate and distinct housing. In this manner, the atmosphere of the housing can be selectively controlled to dry the housing, which limits the extent of moisture that can contact the capacitor element. For example, the moisture content of the atmosphere (expressed as relative humidity) can be about 10% or less, about 5% or less in some embodiments, about 3% or less in some embodiments, and about 0.001 to about 1% in some embodiments. For example, the atmosphere can be gaseous and contain at least one inert gas, for example, nitrogen, helium, argon, xenon, neon, krypton, radon, etc., and mixtures thereof. Typically, inert gases constitute most of the atmosphere in the housing, for example, about 50wt.% to 100wt.% of the atmosphere, about 75wt.% to 100wt.% in some embodiments, and about 90wt.% to about 99wt.% in some embodiments. If desired, a relatively small amount of non-inert gases, for example, carbon dioxide, oxygen, water vapor, etc., can also be used. However, in such cases, the non-inert gas typically constitutes 15 wt.% or less, in some embodiments 10 wt.% or less, in some embodiments about 5 wt.% or less, in some embodiments about 1 wt.% or less, and in some embodiments from about 0.01 wt.% to about 1 wt.% of the atmosphere within the housing.

[0157] The housing may be formed using any of a variety of different materials such as metal, plastic, ceramic, etc. For example, in one embodiment, the housing includes one or more metal layers such as tantalum, niobium, aluminum, nickel, hafnium, titanium, copper, silver, steel (e.g., stainless steel), alloys thereof (e.g., conductive oxides), composites thereof (e.g., metals coated with conductive oxides), etc. In another embodiment, the housing may include one or more ceramic material layers such as aluminum nitride, aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, glass, etc., and combinations thereof.

[0158] The housing may have any desired shape, such as cylindrical, D-shaped, rectangular, triangular, prismatic, etc. For example, referring to Figure 1 , shows an embodiment of a capacitor 100 that includes a housing 122 and a capacitor element 120. In this particular embodiment, the housing 122 is generally rectangular. Typically, the housing and the capacitor element have the same or similar shapes so that the capacitor element can be easily accommodated within the internal cavity. For example, in the embodiment shown, both the capacitor element 120 and the housing 122 have a generally rectangular shape.

[0159] If necessary, the capacitor of the present invention can present a relatively high volumetric efficiency (volumetricefficiency). In order to promote such high efficiency, the capacitor element typically occupies a considerable proportion of the volume of the internal chamber of the housing. For example, the capacitor element can occupy about 30vol.% or more of the internal chamber of the housing, about 50vol.% or more in some embodiments, about 60vol.% or more in some embodiments, about 70vol.% or more in some embodiments, about 80vol.% to about 98vol.% in some embodiments, and about 85vol.% to 97vol.% in some embodiments. For this reason, the difference between the size of the capacitor element and the size of the internal chamber defined by the housing is typically relatively small.

[0160] For example, refer to Figure 1, the capacitor element 120 may have a length (excluding the length of the anode lead 6) that may be relatively similar to the length of the internal chamber 126 defined by the housing 122. For example, the ratio of the length of the anode to the length of the internal chamber ranges from about 0.40 to 1.00, in some embodiments from about 0.50 to about 0.99, in some embodiments from about 0.60 to about 0.99, and in some embodiments from about 0.70 to about 0.98. The capacitor element 120 may have a length of about 5 to about 10 millimeters, and the internal chamber 126 may have a length of about 6 to about 15 millimeters. Similarly, the ratio of the height of the capacitor element 120 (in the z direction) to the height of the internal chamber 126 may range from about 0.40 to 1.00, in some embodiments from about 0.50 to about 0.99, in some embodiments from about 0.60 to about 0.99, and in some embodiments from about 0.70 to about 0.98. In addition, the ratio of the width of capacitor element 120 (in the x-direction) to the width of interior chamber 126 can range from about 0.50 to 1.00, in some embodiments from about 0.60 to about 0.99, in some embodiments from about 0.70 to about 0.99, in some embodiments from about 0.80 to about 0.98, and in some embodiments from about 0.85 to about 0.95. For example, the width of capacitor element 120 can be about 2 to about 7 millimeters and the width of interior chamber 126 can be about 3 to about 10 millimeters, and the height of capacitor element 120 can be about 0.5 to about 2 millimeters and the width of interior chamber 126 can be about 0.7 to about 6 millimeters.

[0161] Although it is absolutely not necessary, the capacitor element can be attached to the housing in the following manner: the anode terminal and the cathode terminal are formed on the outside of the housing so as to be subsequently integrated into the circuit. The specific configuration of the terminal can depend on the intended application. For example, in one embodiment, a capacitor can be formed so that the capacitor is surface mountable and still mechanically stable. For example, the anode lead can be electrically connected to an external surface mountable anode terminal and cathode terminal (e.g., pad, sheet, plate, frame, etc.). Such a terminal can extend through the housing to connect with the capacitor. The thickness or height of the terminal is usually selected to minimize the thickness of the capacitor. For example, the thickness range of the terminal can be from about 0.05 to about 1 mm, from about 0.05 to about 0.5 mm in some embodiments, and from about 0.1 to about 0.2 mm. If necessary, the surface of the terminal can be plated with nickel, silver, gold, tin, etc. as known in the art to ensure that the final component can be mounted on a circuit board. In a specific embodiment, the terminal is deposited with a nickel flash layer and a silver flash layer, respectively, and the mounting surface is also plated with a tin solder layer. In another embodiment, the terminals have a thin outer metal layer (eg, gold) deposited on a base metal layer (eg, copper alloy) to further improve conductivity.

[0162] In certain embodiments, a connective member may be employed within the interior chamber of the housing to facilitate connection to the terminals in a mechanically stable manner. Figure 1 , the capacitor 100 may include a connecting member 162 formed by a first portion 167 and a second portion 165. The connecting member 162 may be formed of a conductive material similar to the external terminals. The first portion 167 and the second portion 165 may be integrated or separate parts connected together directly or via additional conductive elements. In the illustrated embodiment, the second portion 165 is disposed in a plane that is substantially parallel to the lateral direction (e.g., the y-direction) in which the lead 6 extends. The first portion 167 is "upright" in the sense that the first portion 167 is disposed in a plane that is substantially perpendicular to the lateral direction in which the lead 6 extends. In this manner, the first portion 167 can limit the movement of the lead 6 in the horizontal direction to enhance surface contact and mechanical stability during use. If desired, an insulating material 7 (e.g., Teflon) may be employed around the lead 6. TM washer).

[0163] The first portion 167 can have a mounting area (not shown) connected to the anode lead 6. The area can have a "U-shape" to further enhance the surface contact and mechanical stability of the lead 6. The connection of the area to the lead 6 can be achieved using any of a variety of known techniques, such as welding, laser welding, conductive adhesives, etc. For example, in one particular embodiment, the area is laser welded to the anode lead 6. However, no matter which technique is selected, the first portion 167 can maintain the anode lead 6 in a substantially horizontal alignment to further enhance the dimensional stability of the capacitor 100.

[0164] Reference again Figure 1, shows an embodiment of the present invention, in which the connecting member 162 and the capacitor element 120 are connected to the housing 122 via the anode terminal 127 and the cathode terminal 129, respectively. More specifically, the housing 122 of this embodiment includes an outer wall 123 and two opposing side walls 124, between which a chamber 126 including the capacitor element 120 is formed. The outer wall 123 and the side walls 124 can be formed by one or more layers of metal, plastic, or ceramic material as described above. In this particular embodiment, the anode terminal 127 includes a first region 127a and a second region 127b, the first region 127a being located inside the housing 122 and electrically connected to the connecting member 162, and the second region 127b being located outside the housing 122 and providing a mounting surface 201. Likewise, cathode termination 129 includes a first region 129a that is located inside housing 122 and electrically connected to the solid electrolyte of capacitor element 120, and a second region 129b that is located outside housing 122 and provides mounting surface 203. It should be understood that the entire portion of such a region need not be located inside or outside the housing.

[0165] In the illustrated embodiment, conductive trace 127c extends in the outer wall 123 of the housing to connect the first region 127a and the second region 127b. Similarly, conductive trace 129c extends in the outer wall 123 of the housing to connect the first region 129a and the second region 129b. The conductive traces and / or terminal regions can be separate or integrated. In addition to extending through the outer wall of the housing, the traces can also be located in other locations, such as outside the outer wall. Of course, the present invention is by no means limited to the use of conductive traces to form the desired terminals.

[0166] Regardless of the specific configuration, the connection of the terminals 127 and 129 to the capacitor element 120 may be made using any known technique (e.g., welding, laser welding, conductive adhesive, etc.). For example, in one particular embodiment, a conductive adhesive 131 is used to connect the second portion 165 of the connecting member 162 to the anode terminal 127. Similarly, a conductive adhesive 133 is used to connect the cathode of the capacitor element 120 to the cathode terminal 129.

[0167] Optionally, the polymeric constraint may also be positioned in contact with one or more surfaces of the capacitor element, such as a rear surface, a front surface, an upper surface, a lower surface, a side surface, or any combination thereof. The polymeric constraint may reduce the likelihood of the capacitor element delaminating from the housing. In this regard, the polymeric constraint may have a degree of strength that allows the polymeric constraint to maintain the capacitor element in a relatively fixed position even when it is subjected to vibration forces, but the strength is not strong enough to cause the capacitor element to rupture. For example, the constraint may have a tensile strength of about 1 to about 150 megapascals ("MPa") measured at a temperature of about 25°C, in some embodiments about 2 to about 100 MPa, in some embodiments about 10 to about 80 MPa, and in some embodiments about 20 to about 70 MPa. It is generally desirable that the constraint is non-conductive. For example, again referring to Figure 1 , shows an embodiment in which a single polymeric constraint 197 is disposed in contact with the upper surface 181 and the rear surface 177 of the capacitor element 120. Figure 1 A single constraint is shown in FIG, however, it should be understood that a separate constraint can be used to achieve the same function. In fact, more generally, any number of polymer constraints can be used to contact any desired surface of the capacitor element. When multiple constraints are used, they can contact each other or remain physically separated. For example, in one embodiment, a second polymer constraint (not shown) that contacts the upper surface 181 of the capacitor element 120 and the front surface 179 can be used. The first polymer constraint 197 and the second polymer constraint (not shown) can contact each other or may not contact each other. In another embodiment, the polymer constraint can also contact the lower surface 183 and / or the side surface of the capacitor element 120 together with or instead of other surfaces.

[0168] Regardless of how the polymeric constraint is applied, it is typically desirable that the polymeric constraint also be in contact with at least one surface of the housing to help further mechanically stabilize the capacitor element against possible delamination. For example, the constraint may be in contact with the interior surface of one or more sidewalls, an outer wall, a cover, etc. For example, Figure 1 1, polymeric constraint 197 is in contact with interior surface 107 of side wall 124 and interior surface 109 of outer wall 123. Even so, when in contact with the housing, it is desirable that at least a portion of the chamber defined by the housing remain unoccupied, thereby allowing inert gas to flow through the chamber and limiting contact of the solid electrolyte with oxygen. For example, at least about 5% of the volume of the chamber typically remains unoccupied by capacitor elements and polymeric constraints, and in some embodiments, from about 10% to about 50% of the volume of the chamber.

[0169] Once connected in the desired manner, the resulting package is hermetically sealed as described above. Figure 1 , the housing 122 may further include a cover 125, which is placed on the upper surface of the side wall 124 after the capacitor element 120 and the polymer constraint 197 are positioned within the housing 122. The cover 125 may be formed of ceramic, metal (e.g., iron, copper, nickel, cobalt, etc., and alloys thereof), plastic, etc. If desired, a sealing member 187 may be disposed between the cover 125 and the side wall 124 to help provide a good seal. For example, in one embodiment, the sealing member may include a glass-metal seal, Ring (Goodfellow Camridge, Ltd.), etc. The height of the side wall 124 is generally such that the cover 125 does not contact any surface of the capacitor element 120 so that the capacitor element is not contaminated. The polymeric constraint 197 may or may not contact the cover 125. When placed in the desired position, the cover 125 is hermetically sealed to the side wall 124 using known techniques, such as welding (e.g., resistance welding, laser welding, etc.), brazing, etc. The hermetic seal typically occurs in the presence of an inert gas as described above, so that the resulting assembly is substantially free of reactive gases (e.g., oxygen or water vapor).

[0170] It should be understood that the described embodiments are exemplary only, and that various other configurations may be employed in the present invention to hermetically seal the capacitor element within the housing. Figure 2 , shows another embodiment of a capacitor 200, which employs a housing 222 including an outer wall 123 and a cover 225, between which a chamber 126 including a capacitor element 120 and a polymeric restraint 197 is formed. The cover 225 includes an outer wall 223 integrated with at least one side wall 224. For example, in the embodiment shown, two opposing side walls 224 are shown in cross section. The outer walls 223 and 123 both extend in a transverse direction (y-direction) and are generally parallel to each other and to the transverse direction of the anode lead 6. The side wall 224 extends from the outer wall 223 in a longitudinal direction generally perpendicular to the outer wall 123. The distal end 500 of the cover 225 is defined by the outer wall 223, and the proximal end 501 is defined by the flange 253 of the side wall 224.

[0171] The flange 253 extends from the side wall 224 in a lateral direction that can be substantially parallel to the lateral direction of the outer wall 123. The angle between the side wall 224 and the flange 253 can vary, but is typically about 60° to about 120°, in some embodiments about 70° to about 110°, and in some embodiments about 80° to about 100° (e.g., about 90°). The flange 253 also defines a peripheral edge 251 that can be substantially perpendicular to the lateral direction in which the flange 253 and the outer wall 123 extend. The peripheral edge 251 is located outside the periphery of the side wall 224 and can be substantially coplanar with the edge 151 of the outer wall 123. The flange 253 can be sealed to the outer wall 123 using any known technique, such as welding (e.g., resistance welding or laser welding), brazing, gluing, etc. For example, in the illustrated embodiment, a sealing member 287 (e.g., a glass-to-metal seal, In any case, the use of the flanges described above can enable a more stable connection between components and improve the sealing and mechanical stability of the capacitor.

[0172] Other possible housing configurations may also be used in the present invention. For example, Figure 3 shows a similar Figure 2 The capacitor 300 of the housing structure is constructed as shown in FIG. 32, but the terminal pins 327b and 329b are used as external terminals for the anode and cathode, respectively. More specifically, the terminal pin 327a extends through the trace 327c formed in the outer wall 323 and is connected to the anode lead 6 using a known technique (e.g., welding). The additional portion 327a can be used to stabilize the pin 327b. Similarly, the terminal pin 329b extends through the trace 329c formed in the outer wall 323 and is connected to the cathode via the conductive adhesive 133 as described above.

[0173] For only a single capacitor element, the Figure 1-Figure 3 However, it should also be understood that multiple capacitor elements may also be hermetically sealed within the housing. Multiple capacitor elements may be attached to the housing using any of a variety of different techniques. For example, referring to Figure 4, a specific embodiment of a capacitor 400 comprising two capacitor elements is shown, and it will now be described in more detail. More particularly, capacitor 400 includes a first capacitor element 420a electrically connected to a second capacitor element 420b. In this embodiment, the capacitor elements are aligned so that their main surfaces are in a horizontal configuration. That is, the main surface of the capacitor element 420a defined by its width (x direction) and length (y direction) is located adjacent to the corresponding main surface of the capacitor element 420b. Therefore, the main surface is usually coplanar. Alternatively, the capacitor elements can be arranged so that their main surfaces are not coplanar, but perpendicular to each other in a certain direction (e.g., z direction or x direction). Of course, the capacitor elements do not need to extend in the same direction.

[0174] Capacitor elements 420a and 420b are located within a housing 422 that includes an outer wall 423 and side walls 424 and 425 that together define a chamber 426. Although not shown, as described above, a cover can be used that covers the upper surfaces of side walls 424 and 425 and seals assembly 400. Optionally, a polymeric restraint can also be used to help limit vibration of the capacitor elements. For example, in Figure 4 In the embodiment of the present invention, separated polymeric constraints 497a and 497b are respectively located adjacent to capacitor elements 420a and 420b and are in contact with capacitor elements 420a and 420b. Polymeric constraints 497a and 497b can be located at various different positions. In addition, one of the constraints can be removed, or additional constraints can be used. For example, in some embodiments, it may be desirable to use polymeric constraints between capacitor elements to further improve mechanical stability.

[0175] In addition to the capacitor elements, the capacitor also includes an anode terminal electrically connected to the anode lead of each capacitor element and a cathode terminal electrically connected to the cathode of each capacitor element. Figure 4 , capacitor elements connected in parallel with a common cathode terminal 429 are shown. In this particular embodiment, cathode terminal 429 is initially disposed in a plane substantially parallel to the bottom surface of the capacitor element and may be in electrical contact with a conductive trace (not shown). Capacitor 400 also includes connecting members 427 and 527 connected to anode leads 407a and 407b of capacitor elements 420a and 420b, respectively. More particularly, connecting member 427 includes an upright portion 465 and a flat portion 463 connected to an anode terminal (not shown). Similarly, connector 527 includes an upright portion 565 and a flat portion 563 connected to an anode terminal (not shown). Of course, it should be understood that many other types of connecting mechanisms may also be employed.

[0176] The present invention may be better understood with reference to the following examples.

[0177] Testing Procedure

[0178] Equivalent Series Resistance (ESR)

[0179] The equivalent series resistance can be measured using a Keithley 3330 Precision LCZ meter with Kelvin Leads, with a 2.2 volt DC bias and a 0.5 volt peak to peak sinusoidal signal. The operating frequency is 100 kHz and the temperature is 23°C ± 2°C.

[0180] Dissipation coefficient

[0181] The dissipation factor may be measured using a Keithley 3330 Precision LCZ meter with Kelvin Leads, with a 2.2 volt DC bias and a 0.5 volt peak to peak sinusoidal signal. The operating frequency may be 120 Hz and the temperature may be 23°C ± 2°C.

[0182] Leakage Current

[0183] The leakage current can be measured after a minimum of 60 seconds using a leakage tester at a temperature of 23°C ± 2°C and rated voltage.

[0184] capacitance

[0185] To determine capacitance (wet), the sample can be completely immersed in an aqueous phosphoric acid solution with a conductivity of 8,600 μS / cm. The capacitance can then be measured using an Autolab 85429 with a 0.5 volt DC bias and a 0.3 volt peak-to-peak sinusoidal signal. The operating frequency can be 0.5 Hz and the temperature can be 23°C ± 2°C. To determine capacitance (dry), the sample can be dried at 125°C for at least 24 hours, and then the Keithley 3330 Precision LCZ instrument with Kelvin Leads can be used to measure the capacitance with a 2.2 volt DC bias and a 0.5 volt peak-to-peak sinusoidal signal. The operating frequency is 120 Hz and the temperature can be 23°C ± 2°C. The "capacitance recovery rate" can be determined by the following equation:

[0186] Recovery rate (%) = (dry capacitance / wet capacitance) × 100

[0187] Example 1

[0188] Anode samples were formed using 21,000 μFV / g tantalum powder. Each anode sample was embedded with tantalum wire, sintered at 1550°C, and pressed to 5.3 g / cm3 The density of . The size of the resulting pellets was 1.15×1.10×0.60 mm. The pellets were anodized to 77.0 volts at 85° C. in a water / phosphoric acid electrolyte with a conductivity of 8.6 mS to form a dielectric layer. The pellets were anodized again to 150 volts for 25 seconds at 30° C. in water / boric acid / disodium tetraborate with a conductivity of 2.0 mS to form a thicker oxide layer built on the outside. A conductive polymer coating was formed by immersing the anode in an organic solution of polyaniline with a dopant, and then dried at 150° C. for 30 minutes. Thereafter, the entire composition was immersed in a solution containing sulfonic acid and then dried at 150° C. for 30 minutes. This process was repeated 3 times. Thereafter, the component was immersed in a dispersed poly(3,4-ethylenedioxythiophene) having a solid content of 2% and a viscosity of 160 mPa.s. Once coated, the parts were dried at 125°C for 15 minutes. This process was repeated 14 times. The parts were then immersed in a graphite dispersion and dried. Finally, the parts were immersed in a silver dispersion and dried. Multiple parts (400) of 1 μF / 35V capacitors were made in this way.

[0189] Example 2

[0190] Capacitors were formed in the manner described in Example 1, except that once a dielectric comprising a solution of (3-aminopropyl)trimethoxysilane in ethanol (0.33%) was formed, two pre-coating layers of an organometallic compound were used. Thereafter, the component was immersed in a solution of poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-ylmethoxy)-1-butane-sulfonic acid having a solid content of 1.0%. Once coated, the component was dried at 125°C for 15 minutes. This process was repeated 3 times. A conductive polymer coating was formed by immersing the anode in an organic solution of polyaniline with a dopant, and then dried at 150°C for 30 minutes. Thereafter, the entire composition was immersed in a solution comprising sulfonic acid, and And then dried at 150°C for 30 minutes. Repeat this process 3 times. After that, immerse the part in a dispersed poly(3,4-ethylenedioxythiophene) with a solid content of 2% and a viscosity of 160mPa.s. Once coated, dry the part at 125°C for 15 minutes. Repeat this process 14 times. Then immerse the part in a graphite dispersion and dry. Finally, immerse the part in a silver dispersion and dry. In this way, multiple parts (400 pieces) of 1μF / 35V capacitors were made.

[0191] The median results of wet and dry capacitance in μF and the calculation of capacitance recovery rate are shown in Table 1 below.

[0192] Table 1: Capacitance results

[0193] Wet capacitance[uF] Dry capacitance[uF] Capacitance recovery rate [%] Example 1 0.99 0.41 41.4 Example 2 0.99 0.80 80.8

[0194] Without departing from the spirit and scope of the present invention, those of ordinary skill in the art may implement these and other modifications and variations of the present invention. In addition, it should be understood that the various aspects of the various embodiments may be interchangeable in whole or in part. In addition, those of ordinary skill in the art will appreciate that the foregoing description is merely exemplary and is not intended to limit the present invention further described in the appended claims.

Claims

1. A solid electrolytic capacitor, comprising a capacitor element, wherein: The capacitor element comprises: a sintered porous anode body; A dielectric, the dielectric covering the anode body; a pre-coating layer overlying the dielectric, wherein the pre-coating layer comprises an organometallic compound and an intrinsically conductive polymer; and A solid electrolyte overlying the pre-coating layer, wherein the solid electrolyte comprises a conductive polymer having repeating units derived from an aniline monomer having the following general formula (I): in, R5 and R6 are independently hydrogen, alkyl, alkenyl, aryl, alkoxy, aryloxy, alkylthioalkyl, alkaryl, aralkyl, haloalkyl, amino, epoxy, silane, siloxane, alcohol, benzyl, carboxylate, ether, ether carboxylate, ether sulfonate, ester sulfonate, carbamate, or a combination thereof.

2. The solid electrolytic capacitor according to claim 1, wherein: R5 and R6 are hydrogen.

3. The solid electrolytic capacitor according to claim 1, wherein: The solid electrolyte also includes a proton donor.

4. The solid electrolytic capacitor according to claim 3, wherein: The proton donor is an organic acid compound.

5. The solid electrolytic capacitor according to claim 4, wherein: The organic acid compound has the following general formula (VIII): in, m is an integer from 1 to 10; M is hydrogen, an organic free radical, an inorganic free radical, or a combination thereof; X is an anion; R 4 , R 5 and R 6 are independently hydrogen, a hydrocarbon group or R 9 3Si-group, where R 9 are each independently hydrogen or a hydrocarbyl group; and R 7 and R 8 are independently a hydrocarbon group or -(R 10 O) q -R 11 , where q is an integer equal to or greater than 1, R 10 is a hydrocarbon group or a silylene group, R 11 is hydrogen, hydrocarbon or R 12 3Si-, where R 12 Each is independently a hydrocarbon group.

6. The solid electrolytic capacitor according to claim 5, wherein: M is an alkali metal.

7. The solid electrolytic capacitor according to claim 5, wherein: X is SO3.

8. The solid electrolytic capacitor according to claim 5, wherein: R 4 , R 5 and R 6 Each is hydrogen.

9. The solid electrolytic capacitor according to claim 5, wherein: R 7 and R 8 are independently linear or branched C1-C 24 alkyl.

10. The solid electrolytic capacitor according to claim 1, wherein: The solid electrolyte also includes an external dopant.

11. The solid electrolytic capacitor according to claim 10, wherein: The external dopant is a hydroxyphenol compound having one of the following structures (IX), (X), (XI) or (XII): in, n is an integer from 0 to 5; and R is independently C1-C 20 Alkyl, alkenyl, cycloalkyl, aryl, alkaryl, or a combination thereof.

12. The solid electrolytic capacitor according to claim 10, wherein: The external dopant includes methoxyphenol, ethoxyphenol, propoxyphenol, isopropoxyphenol, butoxyphenol, isobutoxyphenol, tert-butoxyphenol, hydroxynaphthalene, cresol, ethylphenol, propylphenol, butylphenol, pentylphenol, 1,6-naphthalene diol, 2,6-naphthalene diol, 2,7-naphthalene diol, or a combination thereof.

13. The solid electrolytic capacitor according to claim 1, wherein: The solid electrolyte also includes a thermal stabilizer.

14. The solid electrolytic capacitor according to claim 13, wherein: The heat stabilizer includes an organic acid.

15. The solid electrolytic capacitor according to claim 1, wherein: The solid electrolyte comprises at least one inner layer including the conductive polymer.

16. The solid electrolytic capacitor according to claim 1, wherein: The solid electrolyte includes at least an outer layer.

17. The solid electrolytic capacitor according to claim 16, wherein: The outer layer is formed from particles comprising a thiophene polymer.

18. The solid electrolytic capacitor according to claim 1, wherein: The pre-coating layer comprises an intrinsically conductive polymer comprising repeating thiophene units.

19. The solid electrolytic capacitor according to claim 18, wherein: The intrinsically conductive polymer comprises a repeating unit of the following formula (V): in, R is (CH2) a -O-(CH2) b -L, where L is a bond or HC([CH2] c H); a is 0 to 10; b is 1 to 18; c is 0 to 10; M is an anion; and X is a cation.

20. The solid electrolytic capacitor according to claim 18, wherein: The intrinsically conductive polymer comprises repeating thiophene units having the following general formula (VII): in a is 0 to 10; b is 1 to 18; R5 is an optionally substituted C1-C6 straight chain or branched alkyl group, or a halogen atom; and X is a hydrogen atom, an alkali metal, NH(R 1 )3, or HNC5H5, wherein R 1 Each is independently a hydrogen atom or an optionally substituted C1-C6 alkyl group.

21. The solid electrolytic capacitor according to claim 20, wherein: a is 1, and b is 3 or 4.

22. The solid electrolytic capacitor according to claim 20, wherein: R5 is methyl.

23. The solid electrolytic capacitor according to claim 20, wherein: X is an alkali metal.

24. The solid electrolytic capacitor according to claim 18, wherein: The repeating thiophene units are formed by sodium 3-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonate Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonic acid Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonate 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, ammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, triethylammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, and combinations thereof.

25. The solid electrolytic capacitor according to claim 18, wherein: The intrinsically conductive polymer has a specific conductivity of 20 S / cm or more.

26. The solid electrolytic capacitor according to claim 1, wherein: The pre-coating layer comprises an organometallic compound.

27. The solid electrolytic capacitor according to claim 26, wherein: The organometallic compound is a monoamino-functional silane having the following general formula (II): in R1, R2 and R3 are independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halogen, haloalkyl or hydroxyalkyl; R4 and R5 are independently hydrogen, alkyl, independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halogen, haloalkyl, hydroxyalkyl, or alternatively N, R4 and R5 together with one or more additional atoms form a ring structure; and Z is an organic group.

28. The solid electrolytic capacitor according to claim 27, wherein: The monoamino-functional silane is a primary amine.

29. The solid electrolytic capacitor according to claim 28, wherein: The primary amine is 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 4-aminobutyltriethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, aminophenyltrimethoxysilane, 3-aminopropyltri(methoxy-ethoxy)silane, 11-aminoundecyltriethoxysilane, 2(4-pyridylethyl)triethoxysilane, 2-(trimethoxysilylethyl)pyridine, N-(3-trimethoxysilylpropyl)pyrrole, 3-(m-aminophenoxypropyltrimethoxysilane), aminopropylsilanetriol, 3-aminopropylmethyldiethoxysilane, 3-aminopropyldiisopropylethoxysilane, 3-aminopropyldimethylethoxysilane, or a combination thereof.

30. The solid electrolytic capacitor according to claim 1, wherein: The pre-coating layer comprises a first layer comprising the organometallic compound and overlying the dielectric, and further wherein the pre-coating layer comprises a second layer comprising the intrinsically conductive polymer and overlying the first layer.

31. The solid electrolytic capacitor of claim 1 further comprising an outer polymer coating overlying the solid electrolyte and comprising conductive polymer particles.

32. The solid electrolytic capacitor according to claim 31, wherein: The conductive polymer particles in the outer polymer coating include a thiophene polymer.

33. The solid electrolytic capacitor according to claim 31, wherein: The outer polymer coating also includes a cross-linking agent.

34. The solid electrolytic capacitor according to claim 1, wherein: The anode body includes tantalum.

35. The solid electrolytic capacitor according to claim 1, wherein: The capacitor element further includes a cathode coating comprising a metal particle layer overlying the solid electrolyte, wherein the metal particle layer includes a plurality of conductive metal particles.

36. The solid electrolytic capacitor according to claim 1, wherein: The capacitor exhibits a recovery rate of 50% or more.

Citation Information

Patent Citations

  • Conductive adhesive agent and process for manufacturing article using the conductive adhesive agent

    US20060038304A1

  • Process for the production of electrolyte capacitors of high nominal voltage

    US20070064376A1

  • Binder removal

    US6197252B1

  • Polythiophene, water-soluble electrically conductive polymer using it, and method for producing it

    US9718905B2

  • Conductive polymer composition

    US9754697B2